Pelletized ethylene / alpha-olefin copolymer product

JP2025500395APending Publication Date: 2025-01-09NOVA CHEM (INT) SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024537809
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-13
Publication Date
2025-01-09

Smart Images

  • Figure 2025500395000001_ABST
    Figure 2025500395000001_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for the preparation of a viscoelastic polymer having a density of 0.865 to 0.905 g / cm3, characterized by unique rheological properties during the transition from the solid to fully molten state. 3 The ethylene / α-olefin copolymer product is described. The ethylene / α-olefin copolymer product comprises a first high density fraction and optionally a second high density fraction, the first high density fraction and the optional second high density fraction having a chemical composition different from the chemical composition of the entire ethylene / α-olefin copolymer product. The first high density fraction further comprises a weight average molecular weight M w,1 HD M w,1 HD and the weight average molecular weight M of the entire ethylene / α-olefin copolymer product. w is M w,1 HD / M w >2 inequality is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Provided herein are ethylene / α-olefin copolymer products that have unique rheological properties during the transition from the solid state to the fully molten state. Pelletized products prepared from the ethylene / α-olefin copolymer products exhibit delayed softening behavior, allowing for higher temperature devolatilization of the pelletized product, thereby reducing the hold-up time required to reach target levels of residual volatile hydrocarbons and significantly reducing operating costs. [Background technology]

[0002] Devolatilization, performed using stripping agents such as air, nitrogen, gaseous hydrocarbons, etc., is a known technique for removing volatile hydrocarbon residues (e.g., unreacted monomers) from solid polymer particles. Those of ordinary skill in the art know that it is desirable to heat the polymer particles in order to accelerate the desorption process of the hydrocarbon residues and to reduce the hold-up time the polymer particles need to remove the hydrocarbon residues. However, for a given polymer composition, there is an upper limit to the devolatilization temperature above which the polymer particles begin to soften and form agglomerates that can clog the devolatilization unit. As a result, there remains a need to develop polymer compositions that retard softening and deformation under devolatilization conditions and retard the onset of agglomerate formation of the polymer particles in order to allow devolatilization at an accelerated rate. Summary of the Invention

[0003] In one embodiment of the present disclosure, an ethylene / α-olefin copolymer product is provided, The ethylene / α-olefin copolymer product is (a) 0.865 to 0.905 g / cm, as measured by ASTM D1505 3 density of, (b) a melt index MI2 of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg; (c) a weight average molecular weight M between 95 and 140 kg / mol, as measured by conventional size exclusion chromatography w , (d) a z-average molecular weight M of 220 to 280 kg / mol, as measured by conventional size exclusion chromatography z , having the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction; The first high density fraction is (i) ΔSCB1 with less than −10 branch points per 1000 carbons; Here, the ΔSCB1 is SCB1 HD - defined according to SCB, SCB1 HD is the short chain branching content of the first high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,1 HD , wherein the weight average molecular weight M of the first high density fraction w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality is satisfied. The present invention is characterized by comprising:

[0004] In one embodiment, the short chain branching content SCB1 of the first high density fraction HD and the weight average molecular weight M of the first high density fraction. w,1 HD are the ΔSCB1>-20 branch points (per 1000 carbons) and M w,1 HD / M w <3 inequality is satisfied.

[0005] In one embodiment, the ethylene / α-olefin copolymer product comprises 0.3 to 0.8 wt.% of a second high density fraction; The second high density fraction is (i) ΔSCB2 with less than −10 branch points per 1000 carbons; Here, the ΔSCB2 is SCB2 HD - defined according to SCB, SCB2 HD is the short chain branching content of the second high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,2 HD , wherein the weight average molecular weight M of the second high density fraction w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w And, 0.8 <M w,2 HD / M w <1.2 inequality is satisfied, The present invention is characterized by comprising:

[0006] In one embodiment, the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fraction in a dynamic temperature sweep test: (a) about 1% to about 3% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; (b) 60% to 80% of a crystalline fraction of said ethylene / α-olefin copolymer product that melts in the temperature range from the RSP to RSP+40° C.; (c) 15%-30% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

[0007] In one embodiment, the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fraction in a dynamic temperature sweep test: (a) about 1% to about 5% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; (b) 60% to 80% of a crystalline fraction of said ethylene / α-olefin copolymer product that melts in the temperature range from the RSP to RSP+40° C.; (c) 10%-20% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

[0008] In one embodiment, the ethylene / α-olefin copolymer product has a modulus of 0.902 g / cm as measured by ASTM D1505. 3 It has the following density:

[0009] In one embodiment, the ethylene / α-olefin copolymer product has a modulus of 0.900 g / cm as measured by ASTM D1505. 3 It has the following density:

[0010] In one embodiment, the ethylene / α-olefin copolymer product has a melt index MI2 of 0.3 to 0.8 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg.

[0011] In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156, z / M w is the ratio of the z-average molecular weight determined by conventional size exclusion chromatography to the weight-average molecular weight, log(ηlin ) is defined according to the following double power law equation: log(η0 lin )=αlog(m b )+βlog(M w LS )+K Where α = -3.8326, β = 3.6954, K = -10.3477, and m b is the molecular weight per backbone bond, m b =[n c M w como +28(1-n c )] / 2, in g / mole, where n c is the mole fraction of α-olefin comonomer measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M w como is the molecular weight of the α-olefin comonomer in g / mol, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion.

[0012] In one embodiment, the ethylene / α-olefin copolymer product is made in a continuous solution phase polymerization process using a single-site catalyst system in two or more reactors, the single-site catalyst system comprising a metallocene catalyst having formula (I): [ka] In the formula, G is a Group 14 element selected from carbon, silicon, germanium, tin, or lead; R is a hydrogen atom, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical, or C 6-10 R2 and R3 are hydrogen atoms, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; R and R are independently selected from hydrogen atoms, unsubstituted C1-20 Hydrocarbyl radicals, substituted C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; Q is independently an activatable leaving group ligand.

[0013] In one embodiment, the ethylene / α-olefin copolymer product is blended with a high density polyethylene to form a polymer blend comprising 97-99.5 wt.% of the ethylene / α-olefin copolymer product and 0.5-3 wt.% of the high density polyethylene, the high density polyethylene having a viscosity of 0.950-0.960 g / cm 3 Density and high load melt index (I 21 ).

[0014] In one embodiment, the ethylene / α-olefin copolymer product and the high density polyethylene each have a complex modulus |G * | and complex viscosity |η * | 1 and complex viscosity |η * | 2 η * | 2 / |η * | 1 <10 inequality is satisfied, or 1<|η * | 2 / |η * | 1 <8 inequality is satisfied.

[0015] In one embodiment, the polymer blend comprises the following crystalline fractions in a dynamic temperature sweep test: (a) about 1% to about 3% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of the polymer blend; (b) 60% to 80% of a crystalline fraction that melts in the temperature range from the RSP of the polymer blend to RSP+40°C; (c) 15%-30% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

[0016] In one embodiment of the present disclosure, a pelletized ethylene / α-olefin copolymer product is provided, comprising an ethylene / α-olefin copolymer product; The ethylene / α-olefin copolymer product is (a) 0.865 to 0.905 g / cm, as measured by ASTM D1505 3 density of, (b) a melt index MI2 of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg; (c) a weight average molecular weight M between 95 and 140 kg / mol, as measured by conventional size exclusion chromatography w , (d) a z-average molecular weight M of 220 to 280 kg / mol, as measured by conventional size exclusion chromatography z , having the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction; The first high density fraction is (i) ΔSCB1 with less than −10 branch points per 1000 carbons; Here, the ΔSCB1 is SCB1 HD - defined according to SCB, SCB1 HD is the short chain branching content of the first high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,1 HD , wherein the weight average molecular weight M of the first high density fraction w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality is satisfied. The present invention is characterized by comprising:

[0017] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product comprising a first high density fraction, the first high density fraction having a short chain branching content SCB1 HD , and weight average molecular weight M w,1 HD and SCB1 HD -SCB>-20, and M w,1 HD / M w <3 inequality.

[0018] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product comprising 0.4 to 0.8 wt.% of a second high density fraction; The second high density fraction is (i) ΔSCB2 with less than −10 branch points per 1000 carbons; Here, the ΔSCB2 is SCB2 HD - defined according to SCB, SCB2 HD is the short chain branching content of the second high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,2 HD , wherein the weight average molecular weight M of the second high density fraction w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w And, 0.8 <M w,2 HD / M w <1.2 inequality is satisfied, The present invention is characterized by comprising:

[0019] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product having a rheological softening point (RSP) of greater than or equal to 55° C. and less than or equal to 95° C., and the ethylene / α-olefin copolymer product comprises the following crystalline fraction in a dynamic temperature sweep test: (a) about 1% to about 5% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; (b) 60% to 80% of a crystalline fraction of said ethylene / α-olefin copolymer product that melts in the temperature range from the RSP to RSP+40° C.; (c) 10%-20% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

[0020] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product having a pelletized elastic modulus of 0.902 g / cm as measured by ASTM D1505. 3 It has the following density:

[0021] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product having a molecular weight of less than 0.900 g / cm as measured by ASTM D1505. 3 It has the following density:

[0022] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product having a molecular weight of less than 0.900 g / cm as measured by ASTM D1505. 3 It has the following density:

[0023] In one embodiment, the pelletized ethylene / α-olefin copolymer product comprises an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product having a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156, z / M w is the ratio of the z-average molecular weight determined by conventional size exclusion chromatography to the weight-average molecular weight, log(η lin ) is defined according to the following double power law equation: log(η0 lin )=αlog(m b )+βlog(M w LS )+K Where α = -3.8326, β = 3.6954, K = -10.3477, and m b is the molecular weight per backbone bond, m b =[n c M w como +28(1-n c )] / 2, in g / mole, where n c is the mole fraction of α-olefin comonomer measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M w como is the molecular weight of the α-olefin comonomer in g / mol, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion. [Brief description of the drawings]

[0024] [Figure 1] 1a and 1b show the non-isothermal crystallization profiles of the ethylene / α-olefin copolymer products of Examples 1-3 and Comparative Examples 1-3 at a cooling rate of 10° C. / min. [Diagram 2]2a-e show the temperature dependence of the elastic shear modulus in the temperature range of 50° C. to 130° C. for Example 1 and Comparative Examples 1-4. The first logarithmic derivative of the elastic shear modulus is also shown for these examples, along with the fitted sum of Gaussian functions (solid lines) and the individual Gaussian terms fitted to the first logarithmic derivative functions (dotted lines). [Diagram 3] FIG. 3 shows the variation of normalized change in gap height as a function of temperature under constant compaction pressure for the pellets of Example 1P and Comparative Examples 1P-4P. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] <Definition> To form a more complete understanding of the present disclosure, the following terms should be defined and used in conjunction with the accompanying drawings and the description of various embodiments throughout.

[0026] As used herein, the term "monomer" refers to a small molecule that can chemically react and combine chemically with itself or other monomers to form a polymer.

[0027] As used herein, the term "α-olefin" is used to describe a monomer having a linear hydrocarbon chain containing 3 to 20 carbon atoms with a double bond at one end of the chain; an equivalent term is "linear α-olefin." As used herein, the term "polyethylene" or "ethylene polymer" refers to a polymer made from ethylene monomer and optionally one or more additional monomers, regardless of the particular catalyst or the particular process used to make the ethylene polymer. In the polyethylene field, the one or more additional monomers are called "comonomers" and often include an α-olefin. The term "homopolymer" generally refers to a polymer containing only one type of monomer. An "ethylene homopolymer" is made using only ethylene as the polymerizable monomer. The term "copolymer" refers to a polymer containing two or more types of monomers. An "ethylene / α-olefin copolymer" is made using ethylene and one or more other polymerizable monomers (e.g., α-olefins).

[0028] Common polyethylenes include high density polyethylene (HDPE), medium density polyethylene (MDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE) or very low density polyethylene (ULDPE), plastomers and elastomers. The term polyethylene also includes polyethylene terpolymers, which contain, in addition to ethylene, two or more comonomers (e.g., α-olefins). The term polyethylene also includes combinations or blends of the above polyethylenes.

[0029] As used herein, the term "linear high density polyethylene" refers to a polyethylene having a molecular weight of about 0.945 g / cm 3 ~Approx. 0.970g / cm 3 The term "polyethylene copolymer" refers to a polyethylene homopolymer or, more preferably, an ethylene / α-olefin copolymer having a density of

[0030] As used herein, the term "high-density fraction" refers to a fraction in a copolymer composition that has a different chemical composition than the other fractions present in the copolymer composition. The term "chemical composition" specifically refers to the number of short chain branches (SCB) per 1000 backbone carbons present in each fraction of the copolymer composition. It is clear that a "high-density fraction" is a fraction that has a different and lower number of short chain branches (SCB) per 1000 backbone carbons present in a copolymer composition than the other fractions present in the copolymer composition.

[0031] As used herein, the terms "hydrocarbyl," "hydrocarbyl radical," or "hydrocarbyl group" refer to linear or cyclic aliphatic, olefinic, acetylenic, and aryl (aromatic) radicals that contain hydrogen and carbons that are deficient in one hydrogen.

[0032] As used herein, "alkyl radical" includes straight-chain, branched, and cyclic paraffin radicals that are deficient in one hydrogen radical, non-limiting examples include methyl (-CH3) and ethyl (-CH2CH3) radicals. The term "alkenyl radical" refers to straight-chain, branched, and cyclic hydrocarbons that contain at least one carbon-carbon double bond that is deficient in one hydrogen radical.

[0033] As used herein, the term "aryl" groups include phenyl, naphthyl, pyridyl, and other radicals in which the molecule has an aromatic ring structure, non-limiting examples include naphthylene, phenanthrene, and anthracene. "Arylalkyl" groups are alkyl groups having an aryl group pendant therefrom, non-limiting examples include benzyl, phenethyl, and tolylmethyl. "Alkylaryl" groups are aryl groups having one or more alkyl groups pendant therefrom, non-limiting examples include tolyl, xylyl, mesityl, and cumyl.

[0034] An "alkoxy" group is an oxy group having an alkyl group pendant therefrom and includes, for example, methoxy, ethoxy, isopropoxy, and the like.

[0035] An "aryloxy" or "aryloxide" group is an oxy group having an aryl group pendant therefrom, and includes, for example, a phenoxy group.

[0036] As used herein, the phrase "heteroatom" includes any atom other than carbon and hydrogen that can be bonded to carbon. A "heteroatom-containing group" is a hydrocarbon radical that contains a heteroatom and may contain one or more of the same or different heteroatoms. In one embodiment, the heteroatom-containing group is a hydrocarbyl group that contains 1 to 3 atoms selected from the group consisting of boron, aluminum, silicon, germanium, nitrogen, phosphorus, oxygen, and sulfur. Non-limiting examples of heteroatom-containing groups include radicals such as imines, amines, oxides, phosphines, ethers, ketones, oxoazoline heterocycles, oxazolines, thioethers, and the like. The term "heterocyclic" refers to a ring system having a carbon skeleton that contains 1 to 3 atoms selected from the group consisting of boron, aluminum, silicon, germanium, nitrogen, phosphorus, oxygen, and sulfur.

[0037] As used herein, the term "unsubstituted" means that a hydrogen radical is attached to the molecular group following the term unsubstituted. The term "substituted" means that the group following the term has one or more moieties (non-hydrogen radicals) replacing one or more hydrogen radicals at any position within the group. Non-limiting examples of moieties include halogen radicals (F, Cl, Br), hydroxyl groups, carbonyl groups, carboxyl groups, silyl groups, amine groups, phosphine groups, alkoxy groups, phenyl groups, naphthyl groups, C1-C 30 Alkyl groups, C2-C 30Non-limiting examples of substituted alkyls and aryls include acyl radicals, alkylsilyl radicals, alkylamino radicals, alkoxy radicals, aryloxy radicals, alkylthio radicals, dialkylamino radicals, alkoxycarbonyl radicals, aryloxycarbonyl radicals, carbomoyl radicals, alkyl- and dialkyl-carbamoyl radicals, acyloxy radicals, acylamino radicals, arylamino radicals, and combinations thereof.

[0038] [Description of the embodiment] <Ethylene / α-olefin copolymer products> In this disclosure, the ethylene / α-olefin copolymer product has a weight average molecular weight M w,1 HD and short chain branching content (SCB1 HD ) distinct from the total ethylene / α-olefin copolymer product.

[0039] In the present disclosure, the ethylene / α-olefin copolymer product has a T onset -T max where T max is the peak crystallization temperature (i.e., the exothermic peak with the maximum heat flow) during the first cooling cycle from the melt at a cooling rate of 10 K / min in the DSC experiment, and T onset is the onset temperature of crystallization, defined according to the point at which the heat-generating DSC signal leaves the high-temperature baseline during the first cooling cycle at a cooling rate of 10 K / min in the DSC experiment. The first cooling thermogram of the ethylene / α-olefin copolymer product is onset and T max At temperatures between max (with a heat flow less than the heat flow of

[0040] In one embodiment, the ethylene / α-olefin copolymer product comprises 0.5 to 2 weight percent of the first high density fraction. In one embodiment, the ethylene / α-olefin copolymer product comprises 0.8 to 2 weight percent of the first high density fraction. In one embodiment, the ethylene / α-olefin copolymer product comprises 1 to 2 weight percent of the first high density fraction. In one embodiment, the ethylene / α-olefin copolymer product comprises 1.5 to 2 weight percent of the first high density fraction.

[0041] In one embodiment, the short chain branching content (SCB1 HD ) is different from and less than the overall short chain branching content (SCB) of the ethylene / α-olefin copolymer product. In one embodiment, the first high density fraction is characterized by having a ΔSCB1 of less than -10 branch points per 1000 carbons, where ΔSCB1 is HD In one embodiment, the first high density fraction is characterized by having a ΔSCB1 of less than -12 branch points per 1000 carbons. In one embodiment, the first high density fraction is characterized by having a ΔSCB1 of less than -15 branch points per 1000 carbons. In one embodiment, the first high density fraction is characterized by having a ΔSCB1 of more than -20 branch points per 1000 carbons.

[0042] The weight average molecular weight (M w,1 HD ) is the weight average molecular weight (M w ) and is greater than or equal to M w,1 HD and M w is M w,1 HD / M w In one embodiment, M w,1 HD and M w is M w,1 HD / M w In one embodiment, M satisfies the inequality w,1 HD and Mw is 2 <M w,1 HD / M w <3 inequality. In one embodiment, M w,1 HD and M w 2.3 <M w,1 HD / M w <3 inequality. In one embodiment, M w,1 HD and M w is 2.5 <M w,1 HD / M w <3 inequality is satisfied.

[0043] In one embodiment, the ethylene / α-olefin copolymer product comprises a second high density fraction, the second high density fraction having a short chain branching content (SCB2) that is different and less than the overall short chain branching content (SCB) of the ethylene / α-olefin copolymer product. HD ) and has a weight average molecular weight M indistinguishable from that of the ethylene / α-olefin copolymer product. w,2 HD The present invention is characterized by having the following.

[0044] In one embodiment, the ethylene / α-olefin copolymer product comprises 0.3 to 0.8 wt.% of the second high density fraction. In one embodiment, the ethylene / α-olefin copolymer product comprises 0.3 to 0.7 wt.% of the second high density fraction. In one embodiment, the ethylene / α-olefin copolymer product comprises 0.3 to 0.6 wt.% of the second high density fraction.

[0045] In one embodiment, the second high density fraction is characterized by having less than -10 branch points per 1000 carbons, where ΔSCB2 is HDIn one embodiment, the second high density fraction is characterized by having a ΔSCB2 of less than -12 branch points per 1000 carbons. In one embodiment, the second high density fraction is characterized by having a ΔSCB2 of greater than -20 branch points per 1000 carbons. In one embodiment, the second high density fraction is characterized by having a ΔSCB2 of greater than -18 branch points per 1000 carbons.

[0046] In one embodiment, M w,2 HD and M w is 0.8 <M w,2 HD / M w <1.2 inequality. In one embodiment, M w,2 HD and M w is 0.9 <M w,2 HD / M w <1.1 inequality. In one embodiment, M w,2 HD and M w is 0.95 <M w,2 HD / M w <1.05 inequality.

[0047] In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product is made in a continuous solution phase polymerization process using a single-site catalyst system in two or more reactors.

[0048] In one embodiment, the ethylene / α-olefin copolymer products of the present disclosure are made in a continuous solution phase polymerization process by polymerizing ethylene and an α-olefin using a single-site catalyst system in the presence of a process solvent in two or more reactors configured in series with one another.

[0049] In one embodiment, the ethylene / α-olefin copolymer products of the present disclosure are made in a continuous solution phase polymerization process by polymerizing ethylene and α-olefins in the presence of a process solvent using a single-site catalyst system in first, second, and third reactors, wherein the first reactor, the second reactor, and the third reactor are configured in series with one another, and the first reactor, the second reactor, and the third reactor are selected from the group consisting of continuous stirred tank reactors and tubular reactors.

[0050] In one embodiment, the ethylene / α-olefin copolymer products of the present disclosure are made in a continuous solution phase polymerization process by polymerizing ethylene and α-olefins in the presence of a process solvent using a single-site catalyst system in a first continuous stirred tank reactor, a second continuous stirred tank reactor, and a first tubular reactor, wherein the first continuous stirred tank reactor, the second continuous stirred tank reactor, and the first tubular reactor are configured in series with one another, and the effluent of the first continuous stirred tank reactor is fed to the second continuous stirred tank reactor and the effluent of the second continuous stirred tank reactor is fed to the first tubular reactor.

[0051] In one embodiment, the second continuous stirred tank reactor is operated at different operating conditions than the first continuous stirred tank reactor, the operating conditions being selected from the group consisting of: agitation speed, composition of the fresh feed fed to the second continuous stirred tank reactor, temperature of the fresh feed fed to the second continuous stirred tank reactor, feed rate of the fresh feed fed to the second continuous stirred tank reactor, and any combination thereof.

[0052] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product is made using a bridged metallocene catalyst having formula (I): [ka] In the formula, G is a Group 14 element selected from carbon, silicon, germanium, tin, or lead; R is a hydrogen atom, C 1-20 Hydrocarbyl radical, C1-20 Alkoxy radical, or C 6-10 R2 and R3 are hydrogen atoms, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; R and R are independently selected from hydrogen atoms, unsubstituted C 1-20 Hydrocarbyl radicals, substituted C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; Q is independently an activatable leaving group ligand.

[0053] In one embodiment, R4 and R5 are independently an aryl group. In one embodiment, R4 and R5 are independently a phenyl group or a substituted phenyl group. In one embodiment, R4 and R5 are a phenyl group. In one embodiment, R4 and R5 are independently a substituted phenyl group. In one embodiment, R4 and R5 are a substituted phenyl group, where the phenyl group is substituted with a substituted silyl group. In one embodiment, R4 and R5 are a substituted phenyl group, where the phenyl group is substituted with a trialkylsilyl group. In one embodiment, R4 and R5 are a substituted phenyl group, where the phenyl group is substituted with a trialkylsilyl group in the para position. In one embodiment, R4 and R5 are a substituted phenyl group, where the phenyl group is substituted with a trimethylsilyl group in the para position. In one embodiment, R4 and R5 are a substituted phenyl group, where the phenyl group is substituted with a triethylsilyl group in the para position. In one embodiment, R4 and R5 are independently an alkyl group. In one embodiment, R4 and R5 are independently an alkenyl group. In one embodiment, R1 is hydrogen. In one embodiment, R1 is an alkyl group. In one embodiment, R1 is an aryl group. In one embodiment, R1 is an alkenyl group.

[0054] In one embodiment, R2 and R3 are independently a hydrocarbyl group having 1 to 30 carbon atoms. In one embodiment, R2 and R3 are independently an aryl group. In one embodiment, R2 and R3 are independently an alkyl group. In one embodiment, R2 and R3 are independently an alkyl group having 1 to 20 carbon atoms. In one embodiment, R2 and R3 are independently a phenyl group or a substituted phenyl group. In one embodiment, R2 and R3 are tert-butyl groups.

[0055] In one embodiment, R2 and R3 are hydrogen. In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product is made using a bridged metallocene catalyst having the formula (II): [ka] where Q is independently an activatable leaving group ligand. In the present disclosure, the term "activatable" means that the ligand Q can be cleaved from the metal center M via a protonolysis reaction or abstracted from the metal center M by a suitable acidic or electrophilic catalytically active compound (also known as a "co-catalyst" compound), respectively, examples of which are described below. The activatable ligand Q can also be converted to another ligand that is cleaved or abstracted from the metal center M (e.g., a halide can be converted to an alkyl group). Without wishing to be bound by a single theory, the protonolysis or abstraction reaction generates an active "cationic" metal center that can polymerize olefins.

[0056] In an embodiment of the present disclosure, the activatable ligand Q is independently selected from the group consisting of: a hydrogen atom; a halogen atom; 1~20 Hydrocarbyl radical, C 1~20 Alkoxy radicals, and C 6-10an aryl or aryloxy radical, where each of the hydrocarbyl, alkoxy, aryl, or aryloxide radicals can be unsubstituted or further substituted with one or more halogens or other groups; 1-8 Alkyl;C 1-8 Alkoxy;C 6-10 aryl or aryloxy; amido or phosphido radicals, but Q is not cyclopentadienyl. Two Q ligands may also be bonded together to form, for example, a substituted or unsubstituted diene ligand (e.g., 1,3-butadiene); or a delocalized heteroatom-containing group, such as an acetate or acetamidinate group.

[0057] In one embodiment of the present disclosure, each Q is a halide atom, C 1~4 is independently selected from the group consisting of an alkyl radical and a benzyl radical.

[0058] In one embodiment, suitable activatable ligands Q are monoanionic, such as halide (eg, chloride) or hydrocarbyl (eg, methyl, benzyl).

[0059] In one embodiment, each activatable ligand Q is a methyl group. In an embodiment, each activatable ligand Q is a benzyl group. In an embodiment, each activatable ligand Q is a chloride group. In one embodiment of the present disclosure, the single-site catalyst used to make the ethylene / α-olefin copolymer is diphenylmethylene(cyclopentadienyl)(2,7-di-t-butylfluorenyl)hafnium dichloride having the following molecular formula: [(2,7-tBu2Flu)Ph2C(Cp)HfCl2].

[0060] In one embodiment of the present disclosure, the single-site catalyst used to make ethylene / α-olefin copolymers is diphenylmethylene(cyclopentadienyl)(2,7-di-t-butylfluorenyl)hafnium dimethyl having the following molecular formula: [(2,7-tBu2Flu)Ph2C(Cp))HfMe2]. In addition to the single-site catalyst molecule itself, the active single-site catalyst system typically further comprises a catalyst activator. In one embodiment of the present disclosure, the catalyst activator comprises an alkylaluminoxane and / or an ionic activator.

[0061] The catalyst activator may optionally include a hindered phenol compound.

[0062] In one embodiment of the present disclosure, the catalyst activator comprises an alkyl aluminum, an ionic activator and a hindered phenol compound.

[0063] The exact structure of alkylaluminoxanes is unknown, but it is generally agreed among experts in the subject matter that they are oligomeric species containing repeating units of the general formula: (R)2AlO-(Al(R)-O) n -Al(R)2 where the R groups may be the same or different and may be linear, branched or cyclic hydrocarbyl radicals containing from 1 to 20 carbon atoms, and n is from 0 to about 50. A non-limiting example of an alkylaluminoxane is methylaluminoxane (or MAO), where each R group is a methyl radical.

[0064] In one embodiment of the present disclosure, R of the alkylaluminoxane is a methyl radical and m is 10 to 40. In one embodiment of the present disclosure, the alkylaluminoxane is a modified methylaluminoxane (MMAO).

[0065] It is well known in the art that alkylaluminoxanes can serve a dual role as both alkylating agents and activators, and therefore alkylaluminoxane catalyst activators are often used in combination with activatable ligands such as halogens.

[0066] Generally, ionic surfactants are composed of a cation and a bulky anion, the latter being substantially non-coordinating. A non-limiting example of an ionic surfactant is a boron ionic surfactant, which is tetracoordinate, having four ligands attached to the boron atom. Non-limiting examples of boron ionic surfactants include several of the formulas shown below: [R 5 ] + [B(R 7 )4] - (In the formula, B represents a boron atom, R 5 is an aromatic hydrocarbyl (e.g., a triphenylmethyl cation), and each R 7 are independently selected from the following: a phenyl radical unsubstituted or substituted with 3 to 5 substituents selected from fluorine atoms, C 1~4 Alkyl or alkoxy radicals and groups of the formula -Si(R 9 ) 3 silyl radicals, where each R 9 is a hydrogen atom and C 1-4 alkyl radicals), and [(R 8 ) t ZH] + [B(R 7 )4] - (wherein B is a boron atom, H is a hydrogen atom, Z is a nitrogen or phosphorus atom, t is 2 or 3, and R 8 is C 1~8 Alkyl radical, unsubstituted or with up to three C 1-4 a phenyl radical substituted with an alkyl radical, or one R 8 may form an anilinium radical together with the nitrogen atom, R 7is defined above).

[0067] In both formulas, R 7A non-limiting example of is the pentafluorophenyl radical. In general, boron ionic activators can be described as salts of tetra(perfluorophenyl)boron, non-limiting examples of which include the anilinium, carbonium, oxonium, phosphonium and sulfonium salts of tetra(perfluorophenyl)boron with anilinium and trityl (or triphenylmethylium). Additional non-limiting examples of ionic activators include triethylammonium tetra(phenyl)boron, tripropylammonium tetra(phenyl)boron, tri(n-butyl)ammonium tetra(phenyl)boron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o-tolyl)boron, tributylammonium tetra(pentafluorophenyl)boron, tripropylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(m,m-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, tri(n-butyl)ammonium tetra(o-tolyl)boron, N,N-dimethylanilinium tetra(phenyl)boron, N,N-diethyl ... anilinium tetra(phenyl) n-butyl boron, N,N-2,4,6-pentamethylanilinium tetra(phenyl) boron, di-(isopropyl)ammonium tetra(pentafluorophenyl) boron, dicyclohexylammonium tetra(phenyl) boron, triphenylphosphonium tetra(phenyl) boron, tri(methylphenyl)phosphonium tetra(phenyl) boron, tri(dimethylphenyl)phosphonium tetra(phenyl) boron, tropylium tetrakis pentafluorophenyl borate, triphenylmethylium tetrakis pentafluorophenyl borate, benzene(diazonium) tetrakis pentafluorophenyl borate, tropylium tetrakis(2,3,5,6-tetrafluorophenyl) borate, triphenylmethylium tetrakis(2,3,5,6-tetrafluorophenyl) borate, benzene(diazonium) tetrakis(3,4,5-trifluorophenyl)borate, tropylium tetrakis(3,4,5-trifluorophenyl)borate, benzene(diazonium)tetrakis(3,4,5-trifluorophenyl)borate, tropylium tetrakis(1,2,2-trifluoroethenyl)borate, triphenylmethylium tetrakis(1,2,2-trifluoroethenyl)borate, benzene(diazonium)tetrakis(1,2,2-trifluoroethenyl)borate, tropylium tetrakis(2,3,4,5-tetrafluorophenyl)borate, triphenylmethylium tetrakis(2,3,4,5-tetrafluorophenyl)borate, and benzene(diazonium)tetrakis(2,3,4,5-tetrafluorophenyl)borate. Readily available commercial ionic activators include N,N-dimethylanilinium tetrakispentafluorophenylborate, and triphenylmethylium tetrakispentafluorophenylborate.

[0068] In one embodiment of the present disclosure, the catalyst activator comprises an ionic activator selected from the group consisting of N,N-dimethylanilinium tetrakispentafluorophenylborate ("[Me2NHPh][B(C6F5)4]"), triphenylmethylium tetrakispentafluorophenylborate (also known as "tritylborate" [Ph3C][B(C6F5)4]"), and trispentafluorophenylboron.

[0069] In one embodiment of the disclosure, the catalyst activator comprises triphenylmethylium tetrakispentafluorophenylborate, "tritylborate."

[0070] In an embodiment of the present disclosure, the catalyst activator comprises a hindered phenol compound selected from the group consisting of butylated phenol antioxidants, butylated hydroxytoluene, 2,6-di-tert-butyl-4-ethylphenol (BHEB), 4,4'-methylenebis(2,6-di-tert-butylphenol), 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, and octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate.

[0071] In one embodiment of the present disclosure, the catalyst activator comprises the hindered phenol compound, 2,6-di-tert-butyl-4-ethylphenol (BHEB).

[0072] Optionally, in embodiments of the present disclosure, a mixture of an alkylaluminoxane and an ionic activator, optionally together with a hindered phenol compound, can be used as a catalyst activator.

[0073] The amounts and molar ratios of the above components of single-site catalyst, alkylaluminoxane, ionic activator, and optional hindered phenol are optimized to produce an active single-site catalyst system.

[0074] In embodiments of the present disclosure, the ionic activator compound may be used in an amount to provide a molar ratio of hafnium (Hf) (single-site catalyst molecule) to boron of 1:1 to 1:10, or 1:1 to 1:6, or 1:1 to 1:2. In embodiments of the present disclosure, the molar ratio of aluminum to hafnium (Hf) (single-site catalyst molecule) in the alkylaluminoxane is from 5:1 to 1000:1, including narrower ranges within this range.

[0075] In an embodiment of the present disclosure, the molar ratio of aluminum in the alkylaluminoxane to the hindered phenol (eg, BHEB) is from 1:1 to 1:0.1, including narrower ranges within this range.

[0076] To produce an active single-site catalyst system, the amounts and molar ratios of the three or four components: single-site catalyst, alkylaluminoxane, ionic activator, and optional hindered phenol are optimized.

[0077] In solution phase polymerization, the monomer is dissolved / dispersed in a solvent before being fed to the reactor (or in the case of gaseous monomers, the monomer may be fed to the reactor and dissolved in the reaction mixture). Before mixing, the solvent and monomer are generally purified to remove potential catalyst poisons such as water, oxygen, metal impurities, etc. Purification of the feedstock follows standard practices in the art. For example, purification of the monomers uses molecular sieves, alumina beds, and oxygen removal catalysts. The solvent itself (e.g., methylpentane, cyclohexane, hexane, or toluene) is preferably treated in a similar manner.

[0078] The feedstock may be heated or cooled before being fed to the reactor.

[0079] Generally, the catalyst components may be premixed in the solvent for the reaction or fed to the reactor as separate streams. In some cases, it may be desirable to premix to allow time for reaction before entering the reaction. Such "in-line mixing" techniques are described in a number of patents in the name of DuPont Canada Inc. (e.g., U.S. Patent No. 5,589,555, issued December 31, 1996).

[0080] Solution polymerization processes for the polymerization or copolymerization of ethylene are well known in the art (see, for example, U.S. Pat. Nos. 6,372,864 and 6,777,509). These processes are carried out in the presence of an inert hydrocarbon solvent. In solution phase polymerization reactors, a variety of solvents can be used as process solvents, non-limiting examples of which include linear, branched or cyclic C5-C 12Examples of suitable catalyst component solvents include alkanes. Non-limiting examples of α-olefins include 1-propene, 1-butene, 1-pentene, 1-hexene, and 1-octene. Suitable catalyst component solvents include aliphatic and aromatic hydrocarbons. Non-limiting examples of aliphatic catalyst component solvents include linear, branched, or cyclic C5-C 12 Aliphatic hydrocarbons include, for example, pentane, methylpentane, hexane, heptane, octane, cyclohexane, cyclopentane, methylcyclohexane, hydrogenated naphtha, or combinations thereof. Non-limiting examples of aromatic catalyst component solvents include benzene, toluene (methylbenzene), ethylbenzene, o-xylene (1,2-dimethylbenzene), m-xylene (1,3-dimethylbenzene), p-xylene (1,4-dimethylbenzene), a mixture of xylene isomers, hemelitene (1,2,3-trimethylbenzene), pseudocumene (1,2,4-trimethylbenzene), mesitylene (1,3,5-trimethylbenzene), a mixture of trimethylbenzene isomers, prehenitene (1,2,3,4-tetramethylbenzene), durene (1,2,3,5-tetramethylbenzene), a mixture of tetramethylbenzene isomers, pentamethylbenzene, hexamethylbenzene, and combinations thereof.

[0081] The polymerization temperature in a conventional solution process may be about 80°C to about 300°C. In one embodiment of the present disclosure, the polymerization temperature in a solution process is about 120°C to about 250°C. The polymerization pressure in a solution process may be a "medium pressure process", which means that the pressure in the reactor is less than about 6,000 psi (about 42,000 kilopascals or kPa). In one embodiment of the present disclosure, the polymerization pressure in a solution process may be about 10,000 to about 40,000 kPa, or about 14,000 to about 22,000 kPa (i.e., about 2000 psi to about 3,000 psi).

[0082] Suitable monomers for copolymerization with ethylene include C 3-20 Preferred comonomers include unsubstituted or up to two C 1-6C substituted by alkyl radicals 3-12 Alpha olefins, unsubstituted or C 1-4 C substituted with up to two substituents selected from the group consisting of alkyl radicals 8-12 Vinyl aromatic monomers, unsubstituted or C 1-4 C substituted with alkyl radicals 4-12 Illustrative non-limiting examples of such alpha-olefins that may be copolymerized with ethylene include one or more of propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 1-decene, styrene, alphamethylstyrene, and constrained cyclic olefins such as cyclobutene, cyclopentene, dicyclopentadiene, norbornene, alkyl-substituted norbornenes, alkenyl-substituted norbornenes, and the like (e.g., 5-methylene-2-norbornene and 5-ethylidene-2-norbornene, bicyclo-(2,2,1)-hepta-2,5-diene).

[0083] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product has from about 3 to about 12 mole % of one or more alpha-olefins.

[0084] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product has from about 3 to about 10 mole % of one or more alpha-olefins.

[0085] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product has from about 3.5 to about 10 mole % of one or more alpha-olefins.

[0086] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and one or more alpha olefins selected from the group including 1-butene, 1-hexene, 1-octene, and mixtures thereof.

[0087] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and one or more alpha olefins selected from the group including 1-hexene, 1-octene, and mixtures thereof.

[0088] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and 1-octene.

[0089] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and at least 1 mol% 1-octene. In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and at least 3 mol% 1-octene. In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and 3-12 mol% 1-octene. In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product comprises ethylene and 3-10 mol% 1-octene.

[0090] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product of the present disclosure has a viscosity of 0.860 g / cm 3 ~0.910g / cm 3 In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product of the present disclosure has a density of 0.908 g / cm 3 In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product of the present disclosure has a density of less than 0.865 g / cm 3 ~0.908g / cm 3 In another embodiment of the present disclosure, the ethylene / α-olefin copolymer product of the present disclosure has a density of 0.905 g / cm 3 In another embodiment of the present disclosure, the ethylene / α-olefin copolymer products of the present disclosure have a density of less than 0.865 g / cm 3 ~0.905g / cm 3 has a density of

[0091] In one embodiment of the present disclosure, the ethylene / α-olefin copolymer product of the present disclosure has a viscosity of 0.865 g / cm3 ~0.905g / cm 3 , or 0.870 g / cm 3 ~0.905g / cm 3 , or 0.875 g / cm 3 ~0.905g / cm 3 , or 0.880 g / cm 3 ~0.905g / cm 3 , or 0.865 g / cm 3 ~0.902g / cm 3 , or 0.870 g / cm 3 ~0.902g / cm 3 , or 0.875 g / cm 3 ~0.902g / cm 3 , or 0.865 g / cm 3 ~0.900g / cm 3 , or 0.870 g / cm 3 ~0.900g / cm 3 , or 0.875 g / cm 3 ~0.900g / cm 3 , or 0.878 g / cm 3 ~0.900g / cm 3 has a density of

[0092] In embodiments of the present disclosure, the melt index I2 of the ethylene / α-olefin copolymer product may be from 0.1 dg / min to 2 dg / min, or from 0.1 dg / min to 1.5 dg / min, or from 0.3 dg / min to 1.5 dg / min, or from 0.3 dg / min to 1.0 dg / min, or from 0.3 dg / min to 0.9 dg / min, or from 0.3 dg / min to 0.8 dg / min.

[0093] In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has a weight average molecular weight M of from about 90,000 to about 200,000 g / mol, or from about 95,000 to about 150,000 g / mol, or from about 95,000 to about 140,000 g / mol, or from about 95,000 to about 125,000 g / mol, or from about 95,000 to about 120,000 g / mol. w has.

[0094] In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has a lower molecular weight distribution M of 1.8, or 2.0, or 2.1, or 2.2, or 2.3. w / M n In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has an upper molecular weight distribution M of 6.0, or 5.5, or 5.0, or 4.5, or 4.0, or 3.75, or 3.5, or 3.0, or 2.5. w / M n In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has a molecular weight distribution M of 2.0 to 4.0, or 2.5 to 4.0, or 2.5 to 3.5. w / M n has.

[0095] In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has a z-average molecular weight M of from about 200,000 to about 300,000 g / mol, or from about 220,000 to about 300,000 g / mol, or from about 220,000 to about 280,000 g / mol, or from about 220,000 to about 270,000 g / mol, or from about 220,000 to about 265,000 g / mol. z has.

[0096] In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product has a ratio of z-average molecular weight to weight average molecular weight, M z / M w has.

[0097] <Long Chain Branching in Ethylene / α-Olefin Copolymer Products> In an embodiment of the present disclosure, the ethylene / α-olefin copolymer product contains long chain branches (hereinafter "LCB"). LCB is a well-known structural phenomenon in ethylene / α-olefin copolymers and is familiar to those skilled in the art. In the present disclosure, the long chain branches are polymeric in nature, i.e., long enough to be confirmed in rheological experiments performed on molten samples.

[0098] In one embodiment, the zero shear viscosity (η) of the ethylene / α-olefin copolymer product is b α M w β has a positive deviation from a double power law relationship of the form b α The term is the molecular weight term M w β Independently, the influence of the type and content of the α-olefin copolymer can be introduced.

[0099] In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156, z / M w is the ratio of the z-average molecular weight determined by conventional SEC to the weight-average molecular weight, log(η0 lin ) is defined according to the following double power law equation:

number

[0100] The zero shear viscosity (η) of ethylene / α-olefin copolymers is determined at 190° C. by fitting the four-parameter Carreau-Yasuda viscosity model to the complex viscosity versus frequency defined by:

number

[0101] In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., where log[η(M z / M w ) 0.4 ]-log(η0 lin In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 linIn one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., where log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.890.

[0102] In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., where log[η(M z / M w ) 0.4 ]-log(η0 lin In one embodiment, the ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )<1.6.

[0103] <Linear viscoelasticity during the melting interval> In one embodiment, the ethylene / α-olefin copolymer product has a rheological softening point (RSP, in °C) that satisfies the following inequality:

number

[0104] In embodiments of the present disclosure, the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or more and 95° C. or less, or 55° C. or more and 90° C. or less, or 55° C. or more and 85° C. or less, or 55° C. or more and 80° C. or less.

[0105] The rheological softening point (RSP) is the absolute value of the first logarithmic derivative (slope) of the elastic shear modulus data in the temperature range above 50°C at a frequency of 1 rad / s (|dlogG' / dT|; in °C) -1 ), where the RSP is the geometric mean of the minimum and maximum absolute slopes (S = √(S min S max The minimum slope (S min ) is the absolute value of the first logarithmic derivative of the elastic shear modulus at 50°C (|dlogG' / dT|). The maximum slope (S max ) is the maximum absolute value of the first logarithmic derivative of the elastic shear modulus (|dlogG' / dT|) observed within the temperature range above 50°C and below 110°C. The elastic shear modulus at 1 rad / s is measured using a multi-frequency temperature sweep test performed on a rotational rheometer during the melting interval with a heating rate of 0.5 K / min. Details regarding the applied test conditions are fully explained in the "Test Methods" section of this disclosure.

[0106] Without wishing to be limited to any theory, it is believed that the slope of the elastic modulus at a given temperature is proportional to the apparent flow activation energy at that temperature. In the pre-softening region, the apparent activation energy is independent of temperature (S min , constant G' slope). The slope at the inflection point (S max ) indicates the maximum apparent activation energy during the temperature softening process. The geometric mean of these slopes allows the onset of softening to be estimated using the average apparent activation energy for processes with large rate changes.

[0107] In the present disclosure, the ethylene / α-olefin copolymer product exhibits delayed softening behavior near and above its rheological softening point. In one embodiment, the ethylene / α-olefin copolymer product comprises 1%-5% of a fraction that melts in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product. In one embodiment, the ethylene / α-olefin copolymer product comprises 3%-5% of a fraction that melts in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product.

[0108] In one embodiment, the ethylene / α-olefin copolymer product comprises 60%-80% of a fraction melting in a temperature range from the RSP of the ethylene / α-olefin copolymer to RSP+40° C. In one embodiment, the ethylene / α-olefin copolymer product comprises 65%-80% of a fraction melting in a temperature range from the RSP of the ethylene / α-olefin copolymer to RSP+40° C. In one embodiment, the ethylene / α-olefin copolymer product comprises 70%-80% of a fraction melting in a temperature range from the RSP of the ethylene / α-olefin copolymer to RSP+40° C.

[0109] In one embodiment, the ethylene / α-olefin copolymer product comprises 8%-20% of a fraction melting in the temperature range of RSP+40° C. to RSP+70° C. In one embodiment, the ethylene / α-olefin copolymer product comprises 10%-20% of a fraction melting in the temperature range of RSP+40° C. to RSP+70° C. In one embodiment, the ethylene / α-olefin copolymer product comprises 12%-20% of a fraction melting in the temperature range of RSP+40° C. to RSP+70° C. In one embodiment, the ethylene / α-olefin copolymer product comprises 16%-20% of a fraction melting in the temperature range of RSP+40° C. to RSP+70° C.

[0110] The percentage of the melted fraction at each temperature interval described in the above embodiment is determined using a mathematical fitting routine including a Gaussian function and an error function. In this disclosure, the first logarithmic derivative (|dlogG' / dT|; in °C) of the elastic shear modulus data obtained at a frequency of 1 rad / s and a heating rate of 0.5 K / min within the temperature range of 50°C to 130°C is used. -1 ) is fitted with a sum of n+2 or n+3 Gaussian functions, where n is the |dlogG' / dT| function (units: °C) when plotted as a function of temperature (T; units: °C). -1 ) is the number of peaks observed in

[0111] Each fitted Gaussian term (i.e., the i-th Gaussian term) is

number

number

[0112] <Polymer blend> Among the particular embodiments of the present disclosure are polymer blends comprising the polyethylene / α-olefin copolymer products described herein and high density polyethylene.

[0113] In one embodiment, the polymer blend comprises 0.5% to 3.0% by weight of high density polyethylene.In one embodiment, the polymer blend comprises 0.5% to 2.0% by weight of high density polyethylene.

[0114] The polymer blend components can be blended using conventional mixing / blending equipment such as single or twin screw extruders; and internal batch mixers such as a BANBURY® mixer; or continuous mixers such as a FARREL® mixer. Mixing times and temperatures can be easily optimized by those skilled in the art without undue experimentation. As a guideline, a mixing temperature of about 150 to about 250° C. is suitable, and a mixing time of about 1 to 20 minutes will provide satisfactory results.

[0115] High density polyethylene, in embodiments of the present disclosure, comprises at least 90%, or at least 95%, or at least 98% by weight ethylene, with the remainder being one or more α-olefins selected from the group consisting of 1-butene, 1-hexene, and 1-octene.

[0116] In one embodiment, the high density polyethylene has a viscosity of 0.950 to 0.960 g / cm 3 , or 0.950~0.955g / cm 3 , or 0.950~0.953g / cm 3In one embodiment, the high density polyethylene has a high load melt index (I) of 5 to 15 dg / min, or 8 to 12 dg / min, or 8.5 to 11.5 dg / min. 21 ).

[0117] One embodiment of the present disclosure includes a polymer blend comprising an ethylene / α-olefin copolymer product described herein and a high density polyethylene, where the complex viscosity (|η * | 1 ) and the complex modulus of elasticity at 10 kPa (|G * |) complex viscosity of high density polyethylene (|η*| 2 ) is 1<|η * | 2 / |η * | 1 <10 inequality, or 1<|η * | 2 / |η * | 1 <8 inequality, or 1<|η * | 2 / |η * | 1 <6 inequality is satisfied.

[0118] In one embodiment, the polymer blend has a rheological softening point (RSP, in °C) that satisfies the following inequality:

number

[0119] In one embodiment, the polymer blend comprises 1% to 3% of a fraction that melts in the temperature range from 50° C. to the RSP of the polymer blend.

[0120] In one embodiment, the polymer blend comprises 60%-80% (or 60%-75%) of a crystalline fraction that melts in the temperature range from the RSP of the polymer blend to RSP+40° C.

[0121] In one embodiment, the polymer blend comprises 15% to 30% (or 20% to 30%) of a crystalline fraction that melts in the temperature range of RSP+40°C to RSP+70°C.

[0122] <Pelletized ethylene / α-olefin copolymer product> The ethylene / α-olefin copolymer product disclosed herein can be converted to a pelletized ethylene / α-olefin copolymer product. In one embodiment, the pelletized ethylene / α-olefin copolymer product is produced by feeding a melt stream of the ethylene / α-olefin copolymer product described herein into an extruder equipped with a die plate at the extruder outlet. Here, the die plate is configured with a plurality of circular holes, thereby resulting in the formation of "spaghetti strands" of extrudate. These strands can be continuously cut by one or more rotating die plate cutters (also referred to by those skilled in the art as "knives") to form pellets. In one embodiment, a melt pump (also referred to as a gear pump) can be positioned between the extruder outlet and the die plate to generate additional pressure without causing overheating. In one embodiment, the die plate cutter is water cooled. The pelletized ethylene / α-olefin copolymer product may contain 1% or more by weight of residual volatile hydrocarbons (e.g., unreacted monomers) after the pelletization step.

[0123] The pellets are conveyed from the die plate using water. A conventional water transport system as described above (i.e., a slurry of pellets in water conveyed through a pipe) is used to move the pelletized ethylene / α-olefin copolymer product to the devolatilization unit and finishing process. Prior to the devolatilization step, a conventional spin dryer may be used to remove water from the slurry. The water removed in the spin dryer can be returned to the die plate cutter for reuse / recycle. The "dry" pelletized ethylene / α-olefin copolymer product is then conveyed to a devolatilization unit to remove residual volatile hydrocarbons (e.g., unreacted monomers) to ppm levels.

[0124] In one embodiment, the devolatilization unit includes a single or multiple vessels, each with upper and lower end walls and a continuous sidewall therebetween, and a stripping agent (e.g., nitrogen gas) is continuously fed upflow using multiple feed nozzles into a first region adjacent the bottom end wall of the devolatilization vessel at a temperature, flow rate, and time sufficient to reduce residual volatile hydrocarbons to ppm levels (e.g., 150 ppm or less) prior to discharging the pelletized ethylene / α-olefin copolymer product from the vessel(s).

[0125] The stripping agent is preferably provided to a first region adjacent to the lower end wall of the vessel(s) at a temperature close to and below the rheological softening point (RSP) of the ethylene / α-olefin copolymer product (e.g., from 10° C. below the RSP of the ethylene / α-olefin copolymer product to the RSP of the resin). Thus, it is desirable for the disclosed pelletized ethylene / α-olefin copolymer product to have a delayed softening behavior to prevent the formation of pellet agglomerates that do not flow easily and / or clog the discharge system of the devolatilization vessel, leading to a stop in the production line. The delayed softening behavior is characterized as a delayed deformation of the pellets under a consolidation pressure (e.g., the pressure exerted by a column of pellets located above any given point in the devolatilization vessel) at a temperature close to the RSP of the resin. This delayed deformation can minimize the necking phenomenon and the formation of adhesive contacts between adjacent pellets.

[0126] Delayed pellet deformation at temperatures near and above the RSP (eg, RSP to RSP+10° C.) may be further desirable in cases where temperature drift occurs within the devolatilization vessel during the devolatilization process.

[0127] In addition to the above advantages, it would be particularly desirable to operate the devolatilization vessel at higher stripping agent inlet temperatures to minimize the hold-up time required to reach target residual volatile hydrocarbon levels and significantly reduce operating costs. A pelletized ethylene / α-olefin copolymer product having delayed deformation would allow the devolatilization process to operate at reduced hold-up times and higher stripping agent inlet temperatures without significant risk of plugging the devolatilization vessel in areas where the pellets are subject to high compaction pressures.

[0128] The pelletized ethylene / α-olefin copolymer products described in this section may optionally include additives and adjuvants, non-limiting examples of which include antiblocking agents, antioxidants, heat stabilizers, slip agents, processing aids, antistatic additives, colorants, dyes, filler materials, light stabilizers, light absorbers, lubricants, pigments, plasticizers, nucleating agents, and combinations thereof.

[0129] <Test Method> Prior to testing, each polymer specimen was conditioned at 23±2° C. and 50±10% relative humidity for at least 24 hours, with subsequent testing being performed at 23±2° C. and 50±10% relative humidity. As used herein, the term "ASTM conditions" refers to a laboratory maintained at 23±2° C. and 50±10% relative humidity, and the specimens to be tested were conditioned in this laboratory for at least 24 hours prior to testing. ASTM refers to the American Society for Testing and Materials.

[0130] <density> The density of the ethylene / α-olefin copolymer products was determined using ASTM D792-13 (November 1, 2013).

[0131] <Melt index> The melt index of the ethylene / α-olefin copolymer products was determined using ASTM D1238 (August 1, 2013). Melt index, I2 and I 21 were measured at 190° C. using weights of 2.16 kg and 21.6 kg, respectively.

[0132] <Conventional Size Exclusion Chromatography (SEC)> Ethylene / α-olefin copolymer product sample (polymer) solutions (1-3 mg / mL) were prepared by heating the polymer in 1,2,4-trichlorobenzene (TCB) and rotating it on a wheel in an oven at 150 °C for 4 h. The antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT) was added to the mixture to stabilize the polymer against oxidative degradation. The BHT concentration was 250 ppm. The polymer solution was chromatographed in a PL220 high temperature chromatography unit equipped with four SHODEX® columns (HT803, HT804, HT805, and HT806) at a flow rate of 1.0 mL / min at 140 °C using TCB as the mobile phase and differential refractive index (DRI) as the concentration detector. To protect the GPC column from oxidative degradation, BHT was added to the mobile phase at a concentration of 250 ppm. The sample injection volume was 200 μL. The GPC column was calibrated with narrow distribution polystyrene standards. Polystyrene molecular weights were converted to polyethylene molecular weights using the Mark-Houwink equation as described in ASTM Standard Test Method D6474-12 (December 2012). The GPC raw data were processed with Cirrus GPC software to obtain molar mass averages (M n , M w , M z ) and molar mass distribution (e.g., M w / M n and M z / M w In the polyethylene art, the commonly used term equivalent to SEC is GPC, i.e., gel permeation chromatography.

[0133] <Light Scattering Size Exclusion Chromatography (LS-SEC)> Ethylene / α-olefin copolymer product sample (polymer) solutions (1-3 mg / mL) were prepared by heating the polymer in 1,2,4-trichlorobenzene (TCB) and rotating it on a wheel in an oven at 150 °C for 4 hours. The antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT) was added to the mixture to stabilize the polymer against oxidative degradation. The BHT concentration was 250 ppm. The sample solution was chromatographed at 140 °C on a PL 220 high temperature chromatography unit equipped with a dual angle light scattering detector (15 degrees and 90 degrees). The SEC columns used were either four SHODEX columns (HT803, HT804, HT805, and HT806) or four PL Mixed ALS or BLS columns. TCB was the mobile phase with a flow rate of 1.0 mL / min, and BHT was added to the mobile phase at a concentration of 250 ppm to protect the SEC column from oxidative degradation. The sample injection volume was 200 μL. The raw SEC data was processed with CIRRUS® GPC software to calculate the absolute molar masses. The "absolute" molar masses (M w LS ) was used to distinguish absolute molar masses determined by LS-SEC from molar masses determined by conventional SEC.

[0134] <Fourier transform infrared (FTIR) spectroscopy> The total amount of comonomer in the ethylene / α-olefin copolymer products was determined by FTIR and reported as short chain branching (SCB) content with a dimension of number of CH3 (methyl branches) per 1000 carbon atoms. This test was completed using compression molded polymer plaques and a Thermo-Nicolet 750 Magna-IR spectrophotometer according to ASTM D6645-01 (2001). Polymer plaques were prepared using a compression molding apparatus (Wabash-Genesis series press) according to ASTM D4703-16 (April 2016).

[0135] <Differential Scanning Calorimetry (DSC)> Differential scanning calorimetry (DSC) was used to obtain the first cooling thermogram of the ethylene / α-olefin copolymer product as follows: first, the instrument was calibrated with indium; after calibration, the ethylene / α-olefin copolymer product sample was equilibrated at 0° C., then the temperature was increased to 200° C. at a heating rate of 10 K / min, then the melt was isothermally held at 200° C. for 5 minutes, and then the melt was cooled to 0° C. at a cooling rate of 10 K / min. The heat flow data obtained during the first cooling cycle described above was then used to calculate the crystallization onset temperature (T onset ), crystallization peak temperature (T max ), and an intermediate exothermic peak occurring between the crystallization onset temperature and the crystallization peak temperature were confirmed.

[0136] <Linear rheology in the molten state> Oscillatory shear measurements at small strain amplitudes were performed to obtain linear viscoelastic functions in the frequency range of 0.02–126 rad / s at 190 °C under N2 atmosphere, 10% strain amplitude, and 5 points per 100 μm. Frequency sweep experiments were performed on a TA Instruments DHR3 stress-controlled rheometer using a cone-plate geometry (Cone-Plate; CP) with a cone angle of 5°, a truncation of 137 μm, and a diameter of 25 mm. In this experiment, a sinusoidal strain wave was applied and the stress response was measured using the complex viscosity (|η * |) and complex modulus (|G * The analysis was carried out in terms of linear viscoelastic functions such as |.

[0137] The zero shear rate viscosity (η0) based on the obtained complex viscosity results was predicted by the four-parameter Carreau-Yasuda model (see K. Yasuda (1979) PhD Thesis, IT Cambridge). The complex viscosity at a complex modulus of 10 kPa is:

number

[0138] High load melt index (I 21 It should be noted that for samples with 100 mm diameter, linear rheological tests were performed at 190 °C, 1.5 mm gap height, 10% strain amplitude, and 5 points / decade in the frequency range 0.2–126 rad / s using a 25 mm parallel plate (PP) geometry. If the torque of the sample approaches the high torque limit of the instrument, the quality of the test data may be compromised by systematic errors related to the compliance of the instrument. Generally, at high frequencies where the stiffness of the sample approaches that of the rheometer, the deformation amplitude applied by the actuator is not fully transmitted to the sample [5]. This may result in a smaller modulus than the true value being measured. To solve this problem, a smaller geometry (i.e., a smaller diameter plate) or smaller strain amplitude can be applied.

[0139] <Rheological Softening Point> To determine the exact moment of softening (i.e., when the elastic shear modulus begins to decrease rapidly), the temperature and frequency dependences of the elastic shear modulus were measured simultaneously over the temperature range from 40 to 140 °C for precrystallized samples cooled from 140 to 40 °C at a cooling rate of 0.5 K / min.

[0140] In this disclosure, the disclosed temperature sweep was carried out using an Anton Paar MCR501 rotational rheometer with a 25 mm parallel plate (PP) geometry. A pre-compression molded disk of ethylene / α-olefin copolymer with a thickness of about 1.9-2 mm was loaded onto the rheometer lower plate at a temperature close to 140°C. After reaching thermal equilibrium at 140°C, the upper plate was lowered and the molten polymer was compressed at a rate of 1000-100 μm / s, with the normal force not exceeding 40 N. The upper plate was lowered to a vertical position 30 μm above the test gap height, the excess molten sample was trimmed, and the gap was lowered to the test position of 1 mm. The temperature was then kept constant and allowed to reach thermal equilibrium at 140 ± 0.1°C. The molten sample was then cooled to 40°C under multi-wave oscillation at a cooling rate of -0.5 K / min, and then heated to 140°C under multi-wave oscillation at a heating rate of +0.5 K / min.

[0141] In these measurements, the strain wave was defined as a superposition of several vibration modes. The resulting stress wave was then decomposed into sinusoidal components, and the stress amplitudes and phase shifts corresponding to each strain wave component were compiled. Linear viscoelastic functions were obtained by a multi-wave oscillation procedure that allows the viscoelastic functions (e.g., elastic shear modulus G') to be measured simultaneously at several frequency levels as a function of temperature during both cooling and heating cycles. To achieve high speed data recording, the fundamental frequency was set at 1 rad / s, and its 2nd, 4th, 7th, 10th, 20th, 40th and 70th harmonics were set. The multi-wave oscillation procedure involves applying a decomposition procedure available in the rheometer software (RHEOPLUS / 32 V3.40) to obtain individual stress waves for each frequency component from the resulting stress wave. Each scan had a duration of 60 s, and a thermal ramp of ±0.5 K / min was applied during the crystallization and melting cycles. The resulting elastic shear modulus G' at 1 rad / s was then numerically differentiated using backward differencing to obtain the absolute value of the first logarithmic derivative function |dlogG' / dT| (in °C) -1) was determined and plotted as a function of temperature (in °C) in the temperature range of 40 °C to 140 °C. The resulting first derivative functions were smoothed using a simple three data point moving average method for further processing. The smoothed first derivative functions were fitted with a sum of n + 2 or n + 3 Gaussian functions in the temperature range of 50 °C to 130 °C, where n is the |dlogG' / dT| function (in °C) when plotted as a function of temperature (T; in °C) using EXCEL SOLVER. -1 ) is the number of peaks observed at the rheological softening point (RSP; i.e., |dlogG' / dT|=√(S min S max ) at which, where, S min is the absolute value of the first logarithmic derivative of the elastic shear modulus at 50°C, and S max is the maximum absolute value of the first logarithmic derivative of the elastic shear modulus observed in the temperature range greater than 50°C and less than 110°C), were interpolated to calculate the integrated area under the first logarithmic derivative function and the corresponding percentage of the crystalline fraction melted in each temperature interval from 50°C to RSP, from RSP to RSP+40°C, and from RSP+40°C to RSP+70°C.

[0142] <Melt strength> Melt strength is measured at 190°C on a Rosand RH-7 capillary rheometer (barrel diameter = 15 mm) using a flat die with a diameter of 2 mm and an L / D ratio of 10:1. Pressure transducer: 10,000 psi (68.95 MPa). Piston speed: 5.33 mm / min. Take-off angle: 52°. Take-off incremental speed: 50-80 m / min. 2 Or 65±15m / min 2 The polymer melt is extruded through a capillary die at a constant rate, and then the polymer strand is drawn off at an increasing take-off rate until it ruptures. The maximum steady value of force in the plateau region of the force versus time curve is defined as the melt strength of the polymer.

[0143] The following examples are presented for the purpose of illustrating selected embodiments of the present disclosure, and it is understood that the presented examples are not intended to limit the scope of the presented claims. EXAMPLES

[0144] <Solution polymerization process> The solution polymerization process conditions for Examples 1-3 and Comparative Examples 1 and 3 are summarized in Tables 1a and 1b, respectively. The ethylene / α-olefin copolymer products of these examples were made in an "in-series" dual continuous stirred tank reactor, "CSTR" reactor solution polymerization process using a single-site catalyst system. In this solution polymerization process, a first and a second CSTR reactor are configured in series with one another, with each reactor receiving a supply of catalyst system components. The dual CSTR reactor system is also followed by a downstream tubular reactor, also configured in series, which receives the outlet stream of the second CSTR reactor, but is not fed additional catalyst system components. The "in-series" "dual CSTR reactor" solution phase polymerization process is described in U.S. Patent Application Publication No. 2019 / 0135958.

[0145] Essentially, in a "series" reactor system, the outlet stream from a first polymerization reactor (R1) flows directly into a second polymerization reactor (R2). The pressure in R1 was about 14 MPa to about 18 MPa, and R2 was operated at a lower pressure to facilitate continuous flow from R1 to R2. Both R1 and R2 were continuously stirred reactors (CSTRs). A third reactor, R3, was also used. The third reactor, R3, was a tubular reactor configured in series with the second reactor, R2 (i.e., the contents of reactor 2 flowed into reactor 3). The process was operated continuously by feeding fresh process solvent, ethylene, 1-octene, and hydrogen to at least the first and second reactors and removing product. Methylpentane was used as the process solvent (a commercially available blend of methylpentane isomers). The first CSTR reactor (R1) had a volume of 3.2 gal (12 L) and the second CSTR reactor (R2) had a volume of 5.8 gal (22 L). The tubular reactor (R3) had a volume of 0.58 gal (2.2 L). The monomer (ethylene) and comonomer (1-octene) were purified using a conventional feed preparation system (such as contact with various absorption media to remove impurities such as water, oxygen, polar contaminants, etc.) prior to addition to the reactors. The reactor feeds were pumped to the reactors in the ratios shown in Tables 1a and 1b. The average residence time in the reactors was calculated by dividing the average flow rate by the reactor volume and is primarily affected by the amount of solvent flowing through each reactor and the total amount of solvent flowing through the solution process. For example, the average reactor residence times were 61 seconds for R1, 73 seconds for R2, and 7.3 seconds for R3, which had a volume of 0.58 gal (2.2 L).

[0146] Ethylene / α-olefin copolymer products were prepared in a first CSTR reactor (R1) configured in series with a second CSTR reactor (R2) using the following single-site catalyst components: diphenylmethylene(cyclopentadienyl)(2,7-di-t-butylfluorenyl)hafnium dimethide [(2,7-tBu2Flu)Ph2C(Cp)HfMe2]; methylaluminoxane (MMAO-07); trityl tetrakis(pentafluoro-phenyl)borate (tritylborate), and 2,6-di-tert-butyl-4-ethylphenol (BHEB). Methylaluminoxane (MMAO-07) and 2,6-di-tert-butyl-4-ethylphenol were premixed in-line and combined with diphenylmethylene(cyclopentadienyl)(2,7-di-t-butylfluorenyl)hafnium dimethide and trityl tetrakis(pentafluorophenyl)borate just before entering the polymerization reactors (e.g., R1 and R2). The efficiency of the single-site catalyst formulation was optimized by adjusting the molar ratios of the catalyst components fed to R1 and R2 and the inlet temperatures of the R1 and R2 catalyst components.

[0147] The total amount of ethylene fed to the solution polymerization process can be divided or split among the three reactors R1, R2 and R3. This manipulated variable is called Ethylene Split (ES), i.e., "ES R1 ", "E.S. R2 " and "ES R3 " refers to the weight percent of ethylene injected into R1, R2, and R3, respectively, where ES R1 +ES R2 +ES R3 = 100%. Similarly, the total amount of 1-octene fed to the solution polymerization process can be divided or split among the three reactors R1, R2 and R3. This manipulated variable is called the octene split (OS), i.e., "OS R1 ", O.S. R2 " and "OS R3 " refers to the weight percent of 1-octene injected into R1, R2, and R3, respectively, except that OS R1 +OS R2 +OSR3 =100%. R1 The term "R" refers to the proportion of ethylene added to R that is converted to copolymer by the catalyst formulation. Similarly, Q R2 and Q R3 "Q" represents the proportion of ethylene added to R2 and R3 that was converted to copolymer in each reactor. T " refers to the total ethylene conversion or overall ethylene conversion throughout a continuous solution polymerization plant - i.e., Q T = 100 × [weight of ethylene in the ethylene / α-olefin copolymer product] / ([weight of ethylene in the ethylene / α-olefin copolymer product] + [weight of unreacted ethylene]).

[0148] In Examples 1 and 3 and Comparative Example 1, ethylene was fed directly to the third reactor R3 (i.e., ethylene split “ES R3 " was not zero for R3). This allowed for the flow of active polymerization catalyst from the second CSTR reactor R2 to the third tubular reactor R3 to continue polymerization in the third reactor. Alternatively, in the case of Example 2 and Comparative Example 3, ethylene was not fed directly to the third reactor R3 (i.e., an ethylene split "ES R3 " was zero), and the extent of polymerization in the third reactor was not significant.

[0149] The polymerization in the continuous solution polymerization process was terminated by adding a catalyst deactivator to the third outlet stream leaving the tubular reactor (R3). The catalyst deactivator used was octanoic acid (caprylic acid) commercially available from P&G Chemicals (Cincinnati, Ohio, USA). The catalyst deactivator was added such that the moles of fatty acid added were 50% of the total moles of catalytic metals and aluminum added to the polymerization process; specifically, moles of octanoic acid added = 0.5 x (moles of hafnium + moles of aluminum).

[0150] A two-stage devolatilization process was used to recover the ethylene / α-olefin copolymer product from the process solvent: two vapor / liquid separators were used to pass the second bottoms stream (from the second V / L separator) through a gear pump / pelletizer combination. The gear pump was a VACOREX® 45 / 45 pump with a capacity of 191 L / h and a 270# steam jacket. The ethylene / α-olefin copolymer product exiting the gear pump passed through a 4-inch diameter static mixer before entering the pelletizer, which forced the ethylene / α-olefin copolymer product from top to bottom through holes in the die plate. The die had 32 holes, each with a diameter of 0.125 inches. The aspect ratio (length to diameter) of each hole was 6.3:1, and the die had a thickness of 1.63 inches and a diameter of 12 inches. The side of the die facing the cooling water system had six cutter knives (OD sweep 8.6878 in., ID sweep 6.2418 in.). There were internal heating channels in the die plate, and the die body and plate were heated with 600# or 270# steam. The cooling water system had a temperature range of 10-80°C and a flow rate of 7500-9500 kg / h.

[0151] DHT-4V (hydrotalcite) supplied by Kyowa Chemical Industry Co., Ltd. (Tokyo, Japan) can be used as a passivator or acid scavenger in the continuous solution process. A slurry of DHT-4V in the process solvent can be added before the first V / L separator.

[0152] Prior to pelletization, the ethylene / α-olefin copolymer product was stabilized by adding 500 ppm Irganox 1076 (primary antioxidant) and 500 ppm IRGAFOS® 168 (secondary antioxidant) based on the weight of the ethylene / α-olefin copolymer product. The antioxidants were dissolved in process solvent and added between the first and second V / L separators.

[0153] Tables 1a and 1b show the reactor conditions used to make each of the ethylene / α-olefin copolymer products of the present invention (Examples 1-3) and Comparative Example 1. Included in Table 1a are process parameters such as the ethylene split and 1-octene split between the reactors (R1, R2, and R3), reactor temperature, ethylene conversion, hydrogen, ethylene, and 1-octene concentrations in the fresh feed to the reactors, total solution rate of the fresh feed, and agitation rates of the CSTR reactors (R1 and R2).

[0154] DSC first cooling thermograms of the ethylene / α-olefin copolymer products of the invention (Examples 1-3) and comparative resins (Comparative Examples 1-3) are shown in Figures 1a and 1b. Comparative Example 2 was QUEO® 8201LA, a plastomeric ethylene / 1-octene resin sold by Borealis AG. Comparative Example 3 was SUPREMETM 891, a plastomeric ethylene / 1-octene copolymer sold by SK Chemical. The density of QUEO 8201LA is about 0.881 g / cm 3 The melt index is about 1.1 g / 10 min. The density of SUPREME 891 is about 0.885 g / cm 3 The melt index is about 1.0 g / 10 min.

[0155] Comparative Example 1 is T onset -T max The process was carried out under process conditions that produced an ethylene / α-olefin copolymer product with a peak crystallization temperature (T max ) is the exothermic peak with the maximum heat flow, and the crystallization onset temperature (T onset ) is the point at which the heat-release DSC signal begins to leave the high temperature baseline. The target density for Comparative Example 1 is 0.885 g / cm 3 ES of Comparative Example 1 R3 and OS R3 was 0.

[0156] Referring to FIG. 1a and Table 1a, the target density is 0.880 g / cm 3In the case of Example 2, where ES 2, no additional polymerizable monomer was added directly to the third reactor (i.e., ES R3 and OS R3 were zero), and the crystallization onset temperature (T onset ) and a peak crystallization temperature (T max ) and T of 27.1°C onset -T max In the case of Example 2, an ethylene / α-olefin copolymer product having T onset and T max A broad heat flow characteristic can also be identified, stretching between 0.880 g / cm and peaking at about 73°C. Example 1 shows 3 At the target density of , reduce the stirring speed of R2 and R3 and OS R3 In Example 1, the crystallization onset temperature (T onset ) is 90.8℃, and the peak crystallization temperature (T max ) is 56.6℃, T onset -T max The temperature was 34.2°C. Example 3 had a target density of 0.885 g / cm 3 Then, reduce the stirring speed of R2 and ES R3 and OS R3 In Example 3, the crystallization onset temperature (T onset ) is 87.6℃, and the peak crystallization temperature (T max ) is 67.0℃, T onset -T max was 20.6℃.

[0157] [Table 1a]

[0158] [Table 1b]

[0159] The Mw, Mn, Mw / Mn, wt%, and branching frequency (i.e., BrF = SCB per 1000 carbons in the polymer backbone) of each component made in the feed zones R1, R2, R3, and R2 and R3 were calculated using reactor model simulations with input conditions adopted for the actual pilot-scale operating conditions and are shown in Tables 2a and 2b. For the multicomponent (or bimodal resin) polyethylene polymer, the M w , M n , and M w / M n was calculated herein by reactor model simulation using input conditions adopted in actual pilot-scale operation. For references on related reactor modeling methods, see A. Hamielec, J. MacGregor, and A. Penlidis, "Copolymerization", Comprehensive Polymer Science and Supplements, Vol. 3, Chapter 2, p. 17, Elsevier, (1996) and JBP Soares and AE Hamielec, "Copolymerization of Olefins in a Series of Continuous Stirred-Tank Slurry-Reactors using Heterogeneous Ziegler-Natta and Metallocene Catalysts I. General Dynamic Mathematical Model", Polymer Reaction Engineering, 4(2&3), p. 153, (1996).

[0160] The model inputs the flow rates of several reactants (e.g., catalyst, monomer such as ethylene, comonomer such as 1-octene, hydrogen, solvent) going to each reactor, the temperature (in each reactor), and the monomer conversion (in each reactor), and calculates the polymer properties (of the polymer made in each reaction zone) using a terminal kinetic model of a series of continuous stirred tank reactors (CSTRs). This "terminal kinetic model" assumes that the reaction rate depends on the monomer unit in the polymer chain where the active catalyst site is located (see A. Hamielec, J. MacGregor, and A. Penlidis, "Copolymerization", Comprehensive Polymer Science and Supplements, Vol. 3, Chapter 2, p. 17, Elsevier, (1996)). In this model, the copolymer chains are assumed to be of reasonably large molecular weight to ensure that the statistics of insertion of monomer / comonomer units at active catalyst centers are valid and that monomer / comonomer consumption by paths other than propagation is negligible. This is known as the "long-chain" approximation.

[0161] The terminal kinetics model for polymerization includes reaction rate equations for activation, initiation, propagation, chain transfer, and deactivation pathways. The model solves steady-state conservation equations (e.g., total material balance and heat balance) for the reacting fluid containing the reactants identified above. The total material balance for a generic CSTR with a given number of inlets and outlets is given by:

number

number

number

[0162] The weight percent of material made in each reaction zone (i.e., R1, R2, and R3 overall, and R2 and R3 feed zones, as presented in Tables 2a and 2b) is determined based on the mass flow rates of monomer and comonomer into each reactor, and the monomer and comonomer conversions in each reactor calculated based on the kinetic reactions. Each reactor feed zone is modeled as a stand-alone CSTR reactor, following the same overall reaction kinetics, except that the monomer concentration in the reactor feed zone will be higher than the concentration in the bulk of the respective reactor. The monomer concentration is calculated based on the feed flow rate and concentration, and a mass balance that includes material exchange with the bulk of the reactor. The former is known, and the latter is calculated based on a hydraulic model developed based on the reactor size, agitator speed, and physical properties of the solution in the feed zone. The reported weight percentage values ​​shown in Tables 2a and 2b are where the weight percentages of materials made in R1, R2, and R3 (i.e., total R1, total R2, and total R3) sum to 100%, and the weight percentages of the fractions made in the R2 and R3 feed zones are reported as a percentage of the total weight of ethylene / α-olefin copolymer product made in the entire system (i.e., total R1+total R2+total R3).

[0163] Degree of polymerization (dp n ) is given by the ratio of the rate of chain propagation reactions to the rate of chain transfer / termination reactions:

number

[0164] The number average molecular weight of the polymer (M n ) is determined from the degree of polymerization and the molecular weight of the monomer units. From the number average molecular weight of the polymer in a given reactor, the molecular weight distribution of the polymer is determined using the following relationship, assuming a Flory-Schultz distribution for single-site catalysts:

number

number

number

[0165] Assuming the Flory-Schultz model, the different moments of the molecular weight distribution can be calculated as follows:

number

number

number

number

number

number

number

[0166] Assuming that the addition of monomer 2 (1-octene) units to chains terminating in octene end units is insignificant, the number of octenes after the ethylene step will be equivalent to the number of ethylenes after the octene step. The branch content BrF per 1000 backbone carbon atoms (500 monomer units) of the resulting polymer is the ratio of the rate of addition of monomer 1 (ethylene) to the rate of addition of monomer 2 (1-octene).

number

[0167] [Table 2a]

[0168] [Table 2b]

[0169] [Table 3-1]

[0170] [Table 3-2]

[0171] By combining the data shown in Tables 2a and 2b with the data shown in Table 3, it can be seen that Examples 1 to 3 have ΔSCB1 less than -10 branch points per 1000 carbons and M w,1 HD / M w It can be observed that the first high density fraction contains ΔSCB1 = 31.0 - 43.5 = -12.5 < -10SCB (carbon 10) produced in the feed zone of R2. 3 (per piece), and M w,1 HD / M w Example 2 contained 1.8 wt% of the fraction where = 295392 / 118404 ≈ 2.5. ΔSCB1 = 26.0 - 45.2 = -19.2 < -10SCB (carbon 10 3 (per piece), and M w,1 HD / M wExample 3 contained 0.6 wt% of the fraction where ΔSCB1 = 25.2 - 40.3 = -15.1 < -10SCB (carbon 10 3 (per piece), and M w,1 HD / M w The first high-density fraction, having a weight average molecular weight M = 292713 / 101923 ≒ 2.9, was contained at 1.7% by weight. w is 95-140 kg / mol, Z average molecular weight M z was 220-280 kg / mol.

[0172] More notably, Comparative Example 1 had a ΔSCB1=22.0-41.0=-19.0<-10SCB (carbon 10 3 (per piece), and M w,1 HD / M w The first high-density fraction, M = 219786 / 89116 ≒ 2.5, was contained at 0.6 wt %. w is less than 95 kg / mol, and M z was outside the range of 220-280 kg / mol.

[0173] Examples 1 and 3 show that the short chain branching content (SCB2) is distinct from and less than the overall short chain branching content (SCB) of the ethylene / α-olefin copolymer product. HD ) and the weight average molecular weight M of the ethylene / α-olefin copolymer product w,2 HD Weight average molecular weight M w,2 HD Specifically, Examples 1 and 3 include a second high density fraction produced in the feed zone of R3, and Example 1 further includes a high density fraction having a ΔSCB2 of 10 carbons. 3 -14.4SCB per piece, M w,2 HD / M w Example 3 includes a second high density fraction characterized by a ΔSCB2 of 1.0 and Example 4 includes a second high density fraction characterized by a ΔSCB2 of 1.0 3-15.1SCB per piece, M w,2 HD / M w A second high density fraction characterized in that the MnO2 concentration is 1.1.

[0174] The process conditions of the continuous solution polymerization process described in Examples 1-3 can be designed to reduce or increase the weight percent, short chain branching content, and molecular weight of the first and second high density fractions produced in the R2 and R3 feed zones compared to the ethylene / α-olefin copolymer product.

[0175] In a large volume CSTR reactor (R2), a portion of the reactor volume adjacent to the monomer feed nozzle has a higher concentration of polymerizable monomer than the bulk of the reactor. Thus, the “feed zone” of R2 produces a first dense fraction with a different short chain branching content and molecular weight than the overall product produced in this reactor. The weight percent of the first dense fraction produced in the R2 feed zone is directly proportional to the size of the feed zone. In addition to the size of the feed zone, the temperature and concentration of the polymerizable monomers (ethylene and 1-octene) in the feed zone can affect the properties of the polymer produced in the feed zone. Assuming the reactor volume, impeller speed, and polymerizable monomer concentration in the fresh feed are constant, a faster feed rate (i.e., TSR of R2) can increase the size of the feed zone and, therefore, the weight percent of the first dense fraction produced in the R2 feed zone. The size of the R2 feed zone can be more effectively increased by decreasing the agitation speed of the second reactor. By increasing the ethylene concentration in the fresh feed (e.g., by injecting a portion of 1-octene and process solvent from a separate feed nozzle), a lower short chain branching content can be further achieved for the first high density fraction produced in the R2 feed zone. Considering the strong temperature sensitivity of the polymerization kinetics, the molecular weight and short chain branching content of the first high density fraction can also be modified by adjusting the temperature of the fresh monomer feed.

[0176] Similarly, for tubular reactor R3, the molecular properties of the second high density fraction produced in the reactor feed zone can be altered by adjusting the ethylene and 1-octene concentrations in the fresh feed, the temperature of the fresh feed, the R3 TSR, etc.

[0177] The pilot-scale examples described in this section have zero-shear viscosities (η) at 190°C calculated as log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156 inequality. For example, referring to Table 3, Example 1 has a zero shear viscosity of 80.8 kPa·s at 190°C, n c is 0.087, M z / M w The ethylene / 1-octene copolymer had a m b =[n c M w como +28(1-n c )] / 2=17.7 g / mol, and the M w como The absolute molecular weight M w LS was 136.0 kg / mol (not shown in Table 4). Therefore, this example is z / M w ) 0.4 ]-log(η0 lin As another example, Example 3 has a zero shear viscosity of 23.9 kPa s at 190°C, n c is 0.081 (or m b 17.3 g / mol), M z / M w 2.2, M w LS is 110.0 kg / mol (not shown in Table 3), and log[η(M z / M w ) 0.4 ]-log(η0 linSimilarly, Example 2 had a zero shear viscosity of 36.4 kPa s at 190°C and n c is 0.09 (or m b is 17.8), Mz / Mw is 2.3, M w LS is 117.0 kg / mol (not shown in Table 3), and log[η(M z / M w ) 0.4 ]-log(η0 lin ) was 0.790.

[0178] Table 4 compares the percentage of the melted fraction at each of the temperature intervals: 50° C. to RSP, RSP to RSP+40° C., and RSP+40° C. to RSP+70° C. As previously described in the Detailed Description section, the percentage of the melted fraction at each of these temperature intervals is determined by integrating the sum of the fitted Gaussian functions within each temperature interval.

[0179] The first logarithmic derivative of the elastic shear modulus data in Example 1 (|dlogG' / dT|; in °C -1 ) (see FIG. 2a) was fitted with a sum of 4 (or n+2, where n is the number of peaks observed when plotting the |dlogG' / dT| function as a function of temperature) Gaussian functions within the temperature range of 50°C to 130°C. The fitted sum of Gaussian functions has G1=2.14, δ1 T =54.7, T1 0 = 62.9°C, first term, G2 = 0.59, δ2 T =9.2, T2 0 = 75.8°C, second term, G3 = 0.34, δ3 T =5.2, T3 0 = 86.4°C, third term, G4 = 0.21, δ4 T =2.3, T4 0 = 118.6 °C. For the determination of the crystalline fraction melted within each temperature interval, the first Gaussian term, which shows a nearly temperature-independent slope behavior within the pre-softening and post-melting regions, was excluded.

[0180] The first logarithmic derivative of the elastic shear modulus data of Comparative Example 1 (|dlogG' / dT|; unit is °C -1 ) (see FIG. 2b) was fitted with a sum of 5 (or n+3, where n is the number of peaks observed when plotting the |dlogG' / dT| function as a function of temperature). The fitted sum of Gaussian functions had G1=2.50, δ1 T =81.4, T1 0 = 59.5°C, first term, G2 = 0.63, δ2 T =10.0, T2 0 = 74.8°C, second term, G3 = 0.72, δ3 T =4.4, T3 0 = 83.6℃, ​​third term, G4 = 0.15, δ4 T =5.6, T4 0 = 105.8°C, 4th term, G5 = 0.01, δ5 T =2.0, T5 0 = 118.1 °C. As above, the first Gaussian term, which shows a slope behavior that is nearly independent of temperature within the pre-softening and post-melting regions, was excluded for the determination of the crystalline fraction melted within each temperature interval.

[0181] The first logarithmic derivative of the elastic shear modulus data of Comparative Example 2 (|dlogG' / dT|; unit is °C -1 ) (see FIG. 2c) was fitted with a sum of 3 (or n+2, where n is the number of peaks observed when plotting the |dlogG' / dT| function as a function of temperature). The fitted sum of Gaussian functions had G1=3.73, δ1 T =121.8, T1 0 = 16.5°C first term, G2 = 0.93, δ2 T =12.7, T2 0 = 77.3°C, second term, G3 = 0.56, δ3 T =4.8, T3 0 = 79.5 ° C. As in Example 1 and Comparative Example 1, the first Gaussian term, which shows a slope behavior that is nearly independent of temperature in the pre-softening and post-melting regions, was excluded for the determination of the crystalline fraction melted within each temperature interval.

[0182] The first logarithmic derivative of the elastic shear modulus data of Comparative Example 3 (|dlogG' / dT|; unit is °C -1 ) (see FIG. 2d) was fitted with a sum of 3 (or n+2, where n is the number of peaks observed when plotting the |dlogG' / dT| function as a function of temperature). The fitted sum of Gaussian functions had G1=4.39, δ1 T =117.4, T1 0 = 12.0°C, first term, G2 = 1.0, δ2 T =11.8, T2 0 = 85.5℃, second term, G3 = 0.53, δ3 T =4.1, T3 0 = 89.5 °C. For the determination of the crystalline fraction melted within each temperature interval, the first Gaussian term was excluded, which shows a slope behavior that is almost independent of temperature within the pre-softening and post-melting regions.

[0183] The first logarithmic derivative of the elastic shear modulus data of Comparative Example 4 (|dlogG' / dT|; unit is °C -1 ) (see FIG. 2e) was fitted with a sum of 3 (or n+2, where n is the number of peaks observed when plotting the |dlogG' / dT| function as a function of temperature). The fitted sum of Gaussian functions had G1=3.98, δ1 T =173.4, T1 0 = 40.5°C, first term, G2 = 0.46, δ2 T =6.3, T2 0 = 63.5°C, second term, G3 = 0.38, δ3 T =16.2, T3 0 = 79.5 °C. For the determination of the crystalline fraction melted within each temperature interval, the first Gaussian term was excluded, which shows a slope behavior that is almost independent of temperature within the pre-softening and post-melting regions.

[0184] As shown in Table 4, Example 1 was clearly observed to have a different softening profile compared to Comparative Examples 1-4, including (a) about 1% to about 3% of a crystalline fraction melting in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer, (b) 60% to 80% of a crystalline fraction melting in the temperature range from the RSP of the ethylene / α-olefin copolymer to RSP+40° C., and (c) 10% to 20% of a fraction melting in the temperature range from RSP+40° C. to RSP+70° C.

[0185] The content of the crystalline fraction melting within the range of RSP+40° C. to RSP+70° C. can be further increased by adding small amounts of high density polyethylene material. In this section, the ethylene / α-olefin copolymer product of Example 1 and two commercially available high density compositions available from NOVA Chemicals, i.e., high load melt index (I 21 ) is 3.1dg / min and density is 0.9550g / cm 3 HB-W355-A and high load melt index (I 21 ) is 10.0 dg / min and density is 0.9515 g / cm 3 A series of polymer blends were made by melt blending the ethylene / α-olefin copolymer product of Example 1 with a high density component within the ranges disclosed in Table 4. The blend compositions and their rheological softening properties are shown in Table 4. Blending the ethylene / α-olefin copolymer product of Example 1 with a high density component within the ranges disclosed in Table 4 did not significantly affect the RSP of the final polymer blend, but it is noteworthy that the percentage of the crystalline fraction melting within the range of RSP+40°C to RSP+70°C increased to values ​​within the range of 20-30%. This increase was accompanied by a decrease in the percentage of the fraction melting within the ranges of 50°C to RSP and RSP to RSP+40°C.

[0186] The complex viscosity ratios of Example 1 and the high density component were 21.9 (|η * | HB-W355-A and |η * | 例1 ), and 4.2(|η * | HB-W952-A and |η * |例1 (ratio of |G at 10 kPa) * |G at 10 kPa * It can be seen that in the polymer blend series with low complex viscosity ratio at |, despite the low density of HB-W952-A, there is a high content of crystalline fraction melting within the range of RSP+40°C to RSP+70°C. This indicates that a better dispersion quality was achieved in the case of the combination Ex. 1 / HB-W952-A, which has a low ratio of the viscosity of the dispersed phase (HB-W952-A) to that of the matrix phase (Ex. 1).

[0187] As mentioned above, pilot-scale Example 1 and Comparative Example 1 were pelletized after the two-stage process for solvent recovery. The pellets produced were spherical and had an average diameter of about 2 millimeters, averaging about 40 pellets per gram of pelletized ethylene / α-olefin copolymer product. The pelletized ethylene / α-olefin copolymer product prepared from Example 1 (the pelletized product is referred to as Example 1P) and the pelletized ethylene / α-olefin copolymer product prepared from Comparative Example 1 (the pelletized product is referred to as Comparative Example 1P), as well as the pellets from the commercially available Comparative Examples 2-4 (referred to as Comparative Examples 2P-4P), were further tested using a rotational rheometer by performing a direct compression test on the pellets with a constant normal force of 9.6±0.5 N (20.4 kPa pressure) applied by the upper plate attached to the torque transducer of the rheometer. The diameter of the upper plate was 25 mm. The pellets were placed on the lower plate of the rheometer, which had the same diameter as the upper plate, at room temperature. The lower plate was surrounded by a cylindrical support ring, which was in contact with the lower plate only at its side area. A pre-weighed pellet sample was loaded into the cavity formed by the lower plate and the inner side area of ​​the support ring, forming a pellet bed 9-12 milliliters high above the lower plate of the rheometer.

[0188] After loading the pellet sample, the top plate was lowered to contact the pellet bed so that a normal force of 9.6±0.5 N was reached, and the rheometer oven was closed and set to 30°C. After 30 minutes, the oven temperature was linearly increased from 30°C to 140°C at a heating rate of 0.5 K / min, and the pellet bed height was monitored as a function of temperature. In this test, the pellets gradually deformed under constant load to fill the spaces between the pellets, which densified the pellet bed and reduced the recorded gap height. The results of such a test procedure are shown in Figure 3 for Example 1 and Comparative Examples 1-4. Figure 3 shows the relationship between the (d-d0) / (d min Figure 1 shows the normalized change in gap height of the pellet bed defined according to (d-d0), where d0 is the initial gap height of the pellet bed, which has a value between 9 and 12 millimeters, d is the instantaneous gap height at any given temperature, and d min is the minimum gap height observed during the experiment and corresponds to the point at which the pellets deform to completely fill the space between the pellets. The normalized gap height in Figure 3 was plotted as a function of T-RSP to eliminate the effect of resin density and provide a fair comparison between the examples.

[0189] It should be noted that at T-RSP of about -35 to -30 °C, the change in the normalized gap height of Comparative Examples 2P to 4P shows an initial initial increase, and then the rate of change becomes much faster at higher T-RSP values. In the case of Example 1P and Comparative Example 1P, the normalized gap height began to increase gently at a T-RSP of about -25 °C. After the initial gentle increase, the curve observed in Comparative Example 1P increased sharply at a T-RSP of about -5 °C and approached the cluster of curves formed by Comparative Examples 2P-4P. This is in contrast to the trend observed in Example 1P, where only a finite amount of pellet deformation and space filling are allowed within the range of -10 < T-RSP < 10. Example 1P can be further distinguished from Comparative Examples 1P to 4P based on the T-RSP value at which complete space filling was achieved. As can be seen, complete space filling was achieved at a T-RSP of about +35 °C in the case of Example 1P, which was at least about 22 °C higher than in the case of the comparative pellets. One advantage of the delayed deformation observed in the case of the pelletized ethylene / α-olefin copolymer product of Example 1P is that devolatilization can be carried out at a temperature close to its RSP without a great risk of clogging the devolatilization vessel.

[0190] While not wishing to be limited by any theory or mechanism, the delayed softening observed in the case of the pelletized ethylene / α-olefin copolymer product of Example 1P can be hypothesized to be a direct result of a transition such as percolation and the formation of a three-dimensional network by interconnected microcrystals of the first and second high-density fractions having a melting temperature much higher than the RSP of the ethylene / α-olefin copolymer product. The long-range and short-range interconnectivity in this network is provided by primary tie molecules (e.g., high-M species of the first high-density fraction having a fold of M / M > 2 in two or more microcrystals) and secondary tie molecules given the optimized overall M and M of the ethylene / α-olefin copolymer product. w,1 HD / M w > 2 and the optimized overall M and M of the ethylene / α-olefin copolymer product. w species) and secondary tie molecules given the optimized overall M and M of the ethylene / α-olefin copolymer product. w and M z of the ethylene / α-olefin copolymer product.

[0191] [Table 4]

[0192] Non-limiting embodiments of the present disclosure include the following.

[0193] <Embodiment A> Ethylene / α-olefin copolymer products having a modulus of 0.865 to 0.905 g / cm as measured by ASTM D1505. 3 a melt index MI2 of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190°C using a load of 2.16 kg; a weight average molecular weight M of 95 to 140 kg / mol, as measured by conventional size exclusion chromatography. w ; z-average molecular weight M of 220 to 280 kg / mol, as determined by conventional size exclusion chromatography; z wherein the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction, the first high density fraction having a ΔSCB1 of less than -10 branch points per 1000 carbons, wherein the ΔSCB1 is HD - defined according to SCB, SCB1 HD is the short chain branching content of the first high density fraction, and SCB is the total short chain branching content of the ethylene / α-olefin copolymer product, as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001), and the weight average molecular weight M w,1 HD (wherein the weight average molecular weight M w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality.

[0194] <Embodiment B> The SCB1 of the first high density fraction HD and M w,1 HD are the ΔSCB1>-20 branch points (per 1000 carbons) and M w,1 HD / M w The ethylene / α-olefin copolymer product as described in embodiment A, wherein the inequality is <3.

[0195] <Embodiment C> The ethylene / α-olefin copolymer product of embodiment A or B, wherein the ethylene / α-olefin copolymer product comprises 0.3 to 0.8 wt.% of a second high density fraction, the second high density fraction having a ΔSCB2 of less than -10 branch points per 1000 carbons (wherein the ΔSCB2 is HD - defined according to SCB, SCB2 HD is the short chain branching content of the second high density fraction, SCB is the total short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001), and the weight average molecular weight M w,2 HD (wherein the weight average molecular weight M w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w And, 0.8 <M w,2 HD / M w <1.2 inequality).

[0196] <Embodiment D> The ethylene / α-olefin copolymer product of embodiment A, B or C, wherein the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fractions in a dynamic temperature sweep test: from about 1% to about 3% of the crystalline fraction melting in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; from 60% to 80% of the crystalline fraction melting in the temperature range from the RSP of the ethylene / α-olefin copolymer product to RSP+40° C.; and from 15% to 30% of the crystalline fraction melting in the temperature range from RSP+40° C. to RSP+70° C.

[0197] <Embodiment E> The ethylene / α-olefin copolymer product of embodiment A, B, or C, wherein the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fractions in a dynamic temperature sweep test: from about 1% to about 5% of the crystalline fraction melting in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; from 60% to 80% of the crystalline fraction melting in the temperature range from the RSP of the ethylene / α-olefin copolymer product to RSP+40° C.; and from 10% to 20% of the crystalline fraction melting in the temperature range from RSP+40° C. to RSP+70° C.

[0198] <Embodiment F> The ethylene / α-olefin copolymer product has a modulus of 0.902 g / cm as measured by ASTM D1505. 3 An ethylene / α-olefin copolymer product according to embodiment A, B, C, D or E, having a density of:

[0199] <Embodiment G> The ethylene / α-olefin copolymer product has a modulus of 0.900 g / cm as measured by ASTM D1505. 3The ethylene / α-olefin copolymer product of embodiment A, B, C, D, or E, having a density of:

[0200] <Embodiment H> The ethylene / α-olefin copolymer product of embodiment A, B, C, D, E, F or G, wherein the melt index, MI2, of the ethylene / α-olefin copolymer product is from 0.3 to 0.8 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg.

[0201] <Embodiment I> An ethylene / α-olefin copolymer product according to embodiment A, B, C, D, E, F, G or H, comprising The ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156, z / M w is the ratio of the z-average molecular weight determined by conventional size exclusion chromatography to the weight-average molecular weight, log(η lin ) is defined according to the following double power law equation: log(η0 lin )=αlog(m b )+βlog(M w LS )+K Where α = -3.8326, β = 3.6954, K = -10.3477, and m b is the molecular weight per backbone bond, m b =[n c M w como +28(1-n c )] / 2, in g / mole, where n c is the mole fraction of α-olefin comonomer measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M wcomo is the molecular weight of the α-olefin comonomer in g / mol, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion.

[0202] <Embodiment J> An ethylene / α-olefin copolymer product according to embodiment A, B, C, D, E, F, G, H or I, comprising The ethylene / α-olefin copolymer product is made in a continuous solution phase polymerization process in two or more reactors using a single-site catalyst system, the single-site catalyst system comprising a metallocene catalyst having formula (I): [ka] (wherein G is a Group 14 element selected from carbon, silicon, germanium, tin or lead; R is a hydrogen atom, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical, or C 6-10 R2 and R3 are hydrogen atoms, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; R and R are independently selected from hydrogen atoms, unsubstituted C 1-20 Hydrocarbyl radicals, substituted C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; Q is independently an activatable leaving group ligand.

[0203] <Embodiment K> 1. A pelletized ethylene / α-olefin copolymer product comprising an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product having a pelletized elastic modulus of 0.865 to 0.905 g / cm as measured by ASTM D1505. 3a melt index MI2 of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190°C using a load of 2.16 kg; a weight average molecular weight M of 95 to 140 kg / mol, as measured by conventional size exclusion chromatography. w ; z-average molecular weight M of 220 to 280 kg / mol, as determined by conventional size exclusion chromatography; z wherein the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction, the first high density fraction having a ΔSCB1 of less than -10 branch points per 1000 carbons, wherein the ΔSCB1 is HD - defined according to SCB, SCB1 HD is the short chain branching content of the first high density fraction, and SCB is the total short chain branching content of the ethylene / α-olefin copolymer product, as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001), and the weight average molecular weight M w,1 HD (wherein the weight average molecular weight M w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality.

[0204] <Embodiment L> The SCB1 of the first high density fraction HD and M w,1 HD are SCB1, respectively. HD -SCB>-20 branch points (per 1000 carbons), and M w,1 HD / M w The pelletized ethylene / α-olefin copolymer product according to embodiment K, wherein the pelletized ethylene / α-olefin copolymer product satisfies the inequality of <3.

[0205] <Embodiment M> The pelletized ethylene / α-olefin copolymer product of embodiment K or L, wherein the ethylene / α-olefin copolymer product comprises 0.4 to 0.8 wt.% of a second high density fraction, the second high density fraction having a ΔSCB2 of less than -10 branch points per 1000 carbons, where the ΔSCB2 is HD - defined according to SCB, SCB2 HD is the short chain branching content of the second high density fraction, SCB is the total short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001), and the weight average molecular weight M w,2 HD (wherein the weight average molecular weight M w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w And, 0.8 <M w,2 HD / M w <1.2 inequality).

[0206] <Embodiment N> The pelletized ethylene / α-olefin copolymer product of embodiment K, L, or M, wherein the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fractions in a dynamic temperature sweep test: from about 1% to about 5% of the crystalline fraction melting in the temperature range from 50° C. to the RSP of the ethylene / α-olefin copolymer product; from 60% to 80% of the crystalline fraction melting in the temperature range from the RSP of the ethylene / α-olefin copolymer product to RSP+40° C.; and from 10% to 20% of the crystalline fraction melting in the temperature range from RSP+40° C. to RSP+70° C.

[0207] <Embodiment O> The ethylene / α-olefin copolymer product has a modulus of 0.902 g / cm as measured by ASTM D1505. 3 The pelletized ethylene / α-olefin copolymer product of embodiment K, L, M or N having a density of:

[0208] <Embodiment P> The ethylene / α-olefin copolymer product has a modulus of 0.900 g / cm as measured by ASTM D1505. 3 The pelletized ethylene / α-olefin copolymer product of embodiment K, L, M or N having a density of:

[0209] <Embodiment Q> The pelletized ethylene / α-olefin copolymer product of embodiment K, L, M, N, O or P, wherein the melt index, MI2, of the ethylene / α-olefin copolymer product is from 0.3 to 0.8 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg.

[0210] <Embodiment R> A pelletized ethylene / α-olefin copolymer product according to embodiment K, L, M, N, O, P or Q, comprising The ethylene / α-olefin copolymer product has a zero shear viscosity (η) at 190° C., log[η(M z / M w ) 0.4 ]-log(η0 lin )>0.156, z / M w is the ratio of the z-average molecular weight determined by conventional size exclusion chromatography to the weight-average molecular weight, log(η lin ) is defined according to the following double power law equation: log(η0 lin )=αlog(m b )+βlog(M w LS )+K Where α = -3.8326, β = 3.6954, K = -10.3477, and m b is the molecular weight per backbone bond, m b =[n c M w como +28(1-n c )] / 2, in g / mole, where n c is the mole fraction of α-olefin comonomer measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M w como is the molecular weight of the α-olefin comonomer in g / mol, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion.

[0211] <Embodiment S> A polymer blend comprising 97 to 99.5 wt. % of an ethylene / α-olefin copolymer product according to embodiment A, B, C, D, E, F, G, H, I or J, and 0.5 to 3 wt. % of a high density polyethylene, High density polyethylene is 0.950-0.960g / cm 3 Density and high load melt index (I 21 ).

[0212] <Embodiment T> The ethylene / α-olefin copolymer product and the high density polyethylene each have a complex modulus of elasticity |G * | and complex viscosity |η * | 1 and complex viscosity |η * | 2 η * | 2 / |η * | 1 The polymer blend of embodiment S, wherein the polymer blend satisfies the inequality: <10.

[0213] <Embodiment U> The ethylene / α-olefin copolymer product and the high density polyethylene each have a complex modulus of elasticity |G * | and complex viscosity |η * | 1 and complex viscosity |η * | 2 η * | 2 / |η * | 1 The polymer blend of embodiment S, wherein the polymer blend satisfies the inequality: <8.

[0214] <Embodiment V> The polymer blend of embodiment S, T or U, comprising the following crystalline fractions in a dynamic temperature sweep test: from about 1% to about 3% of the crystalline fraction melting in the temperature range from 50°C to the RSP of the polymer blend; from 60% to 80% of the crystalline fraction melting in the temperature range from the RSP of the polymer blend to RSP+40°C; from 15% to 30% of the crystalline fraction melting in the temperature range from RSP+40°C to RSP+70°C. [Industrial Applicability]

[0215] Disclosed herein are ethylene / α-olefin copolymer products that have a wide variety of industrial uses, non-limiting examples of which include the preparation of sealant layers in multi-layer flexible packaging films.

Claims

1. 1. An ethylene / α-olefin copolymer product comprising: (a) 0.865 to 0.905 g / cm3 as measured by ASTM D1505 3 density of, (b) a melt index, MI, of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg. 2 , (c) a weight average molecular weight M of 95 to 140 kg / mol, as measured by conventional size exclusion chromatography. w , (d) a z-average molecular weight M of 220 to 280 kg / mol, as measured by conventional size exclusion chromatography. z , having the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction; The first high density fraction is (i) ΔSCB of less than −10 branch points per 1000 carbons 1 , Here, the Δ 1 , S.C.B. 1 HD - defined according to SCB, SCB 1 HD is the short chain branching content of the first high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,1 HD , wherein the weight average molecular weight M of the first high density fraction w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality is satisfied.

1. An ethylene / α-olefin copolymer product comprising:

2. The SCB of the first high density fraction 1 HD and M. w,1 HD are ΔSCB, respectively. 1 >-20 branch points (per 1000 carbons), and M w,1 HD / M w The ethylene / α-olefin copolymer product of claim 1 , wherein the ethylene / α-olefin copolymer product satisfies the inequality:

3. 3. The ethylene / α-olefin copolymer product of claim 1 or 2, the ethylene / α-olefin copolymer product comprises 0.3 to 0.8 wt. % of a second high density fraction; The second high density fraction is (i) ΔSCB of less than −10 branch points per 1000 carbons 2 , Here, the Δ 2 , S.C.B. 2 HD - defined according to SCB, SCB 2 HD is the short chain branching content of the second high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,2 HD , wherein the weight average molecular weight M of the second high density fraction w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w However, 0.8<M w,2 HD / M w <1.2 inequality is satisfied.

1. An ethylene / α-olefin copolymer product comprising:

4. 4. The ethylene / α-olefin copolymer product of any one of claims 1 to 3, The ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55° C. or greater and 95° C. or less, and the ethylene / α-olefin copolymer product contains the following crystalline fraction in a dynamic temperature sweep test: (a) about 1% to about 5% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of said ethylene / α-olefin copolymer product; (b) 60% to 80% of a crystalline fraction that melts in the temperature range from the RSP of the ethylene / α-olefin copolymer product to RSP+40° C.; (c) 10% to 20% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

5. The ethylene / α-olefin copolymer product has a modulus of 0.902 g / cm as measured by ASTM D1505. 3 The ethylene / α-olefin copolymer product of any one of claims 1 to 4, having a density of:

6. The ethylene / α-olefin copolymer product has a modulus of 0.900 g / cm as measured by ASTM D1505. 3 The ethylene / α-olefin copolymer product of any one of claims 1 to 4, having a density of:

7. The melt index MI of the ethylene / α-olefin copolymer product 2 The ethylene / α-olefin copolymer product of any one of claims 1 to 6, having a modulus of elasticity of 0.3 to 0.8 dg / min as measured by ASTM D1238 at a temperature of 190°C using a load of 2.16 kg.

8. 8. The ethylene / α-olefin copolymer product of any one of claims 1 to 7, The ethylene / α-olefin copolymer product has a zero shear viscosity (η 0 ), and log[η 0 (M z / M w ) 0.4 ]-log(η 0 lin )>0.156, z / M w is the ratio of the z-average molecular weight to the weight-average molecular weight as determined by conventional size exclusion chromatography, and log(η 0 lin ) is defined according to the double power law equation: log (the) 0 lin )=alog(m b )+blog(M w LS )+K In the formula, α=-3.8326, β=3.6954, K=-10.3477, and m b is the molecular weight per backbone bond, m b = [n c M w como +28(1-n c ) / 2, where n c is the mole fraction of α-olefin comonomer as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M w como is the molecular weight of the α-olefin comonomer in g / mole, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion.

9. 9. The ethylene / α-olefin copolymer product of any one of claims 1 to 8, The ethylene / α-olefin copolymer product is made in a continuous solution phase polymerization process in two or more reactors using a single-site catalyst system, the single-site catalyst system comprising a metallocene catalyst having formula (I): 【Chemistry 1】 wherein G is a Group 14 element selected from carbon, silicon, germanium, tin or lead; R 1 is a hydrogen atom, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical, or C 6-10 is an aryloxide radical; R 2 and R 3 is a hydrogen atom, C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; R 4 and R 5 is a hydrogen atom, unsubstituted C 1-20 Hydrocarbyl radical, substituted C 1-20 Hydrocarbyl radical, C 1-20 Alkoxy radical or C 6-10 aryloxide radicals; Q is independently an activatable leaving group ligand.

10. 10. A polymer blend comprising 97 to 99.5 wt. % of the ethylene / α-olefin copolymer product of any one of claims 1 to 9 and 0.5 to 3 wt. % of a high density polyethylene, High density polyethylene is 0.950 to 0.960 g / cm 3 and a high load melt index (I 21 ).

11. The ethylene / α-olefin copolymer product and the high density polyethylene each have a complex modulus |G * | and complex viscosity |η * | 1 and complex viscosity |η * | 2 having 1<|the * | 2 / |the * | 1 <10 The polymer blend of claim 10, wherein the polymer blend satisfies the inequality:

12. The ethylene / α-olefin copolymer product and the high density polyethylene each have a complex modulus |G * | and complex viscosity |η * | 1 and complex viscosity |η * | 2 having 1<|the * | 2 / |the * | 1 <8 The polymer blend of claim 10, wherein the polymer blend satisfies the inequality:

13. The polymer blend according to any one of claims 10 to 12, comprising the following crystalline fractions in a dynamic temperature sweep test: (d) about 1% to about 3% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of the polymer blend; (e) 60% to 80% of a crystalline fraction that melts in the temperature range from the RSP of the polymer blend to RSP+40° C.; (f) 15% to 30% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

14. 1. A pelletized ethylene / α-olefin copolymer product comprising an ethylene / α-olefin copolymer product, the ethylene / α-olefin copolymer product comprising: (a) 0.865 to 0.905 g / cm3 as measured by ASTM D1505 3 density of, (b) a melt index, MI, of 0.3 to 1.5 dg / min, as measured by ASTM D1238 at a temperature of 190° C. using a load of 2.16 kg. 2 , (c) a weight average molecular weight M of 95 to 140 kg / mol, as measured by conventional size exclusion chromatography. w , (d) a z-average molecular weight M of 220 to 280 kg / mol, as measured by conventional size exclusion chromatography. z , having the ethylene / α-olefin copolymer product comprises 0.5 to 2 wt. % of a first high density fraction; The first high density fraction is (i) ΔSCB of less than −10 branch points per 1000 carbons 1 , Here, the Δ 1 , S.C.B. 1 HD - defined according to SCB, SCB 1 HD is the short chain branching content of the first high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,1 HD , wherein the weight average molecular weight M of the first high density fraction w,1 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w But, M w,1 HD / M w >2 inequality is satisfied. Pelletized ethylene / α-olefin copolymer product.

15. The SCB of the first high density fraction 1 HD and M. w,1 HD are SCBs, respectively. 1 HD -SCB>-20 branch points (per 1000 carbons), and M w,1 HD / M w 15. The pelletized ethylene / α-olefin copolymer product of claim 14, satisfying the inequality: <3.

16. 16. The pelletized ethylene / α-olefin copolymer product of claim 14 or 15, the ethylene / α-olefin copolymer product comprises 0.4 to 0.8 wt. % of a second high density fraction; The second high density fraction is (i) ΔSCB of less than −10 branch points per 1000 carbons 2 , Here, the Δ 2 , S.C.B. 2 HD - defined according to SCB, SCB 2 HD is the short chain branching content of the second high density fraction, and SCB is the overall short chain branching content of the ethylene / α-olefin copolymer product as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01(2001); and (ii) Weight average molecular weight M w,2 HD , wherein the weight average molecular weight M of the second high density fraction w,2 HD and the weight average molecular weight M of the ethylene / α-olefin copolymer product. w However, 0.8<M w,2 HD / M w <1.2 inequality is satisfied.

1. A pelletized ethylene / α-olefin copolymer product comprising:

17. 17. The pelletized ethylene / α-olefin copolymer product of any one of claims 14 to 16, wherein the ethylene / α-olefin copolymer product has a rheological softening point (RSP) of 55°C or more and 95°C or less, and the ethylene / α-olefin copolymer product comprises the following crystalline fraction in a dynamic temperature sweep test: (a) about 1% to about 5% of a crystalline fraction that melts in the temperature range from 50° C. to the RSP of said ethylene / α-olefin copolymer product; (b) 60% to 80% of a crystalline fraction that melts in the temperature range from the RSP of the ethylene / α-olefin copolymer product to RSP+40° C.; (c) 10% to 20% of the crystalline fraction melts in the temperature range from RSP+40°C to RSP+70°C.

18. The ethylene / α-olefin copolymer product has a modulus of 0.902 g / cm as measured by ASTM D1505. 3 18. The pelletized ethylene / α-olefin copolymer product of any one of claims 14 to 17, having a density of:

19. The ethylene / α-olefin copolymer product has a modulus of 0.900 g / cm as measured by ASTM D1505. 3 18. The pelletized ethylene / α-olefin copolymer product of any one of claims 14 to 17, having a density of:

20. The melt index MI of the ethylene / α-olefin copolymer product 2 20. The pelletized ethylene / α-olefin copolymer product of any one of claims 14 to 19, wherein the pellet toughness is 0.3 to 0.8 dg / min as measured by ASTM D1238 at a temperature of 190°C using a load of 2.16 kg.

21. 21. The pelletized ethylene / α-olefin copolymer product of any one of claims 14 to 20, The ethylene / α-olefin copolymer product has a zero shear viscosity (η 0 ), and log[η 0 (M z / M w ) 0.4 ]-log(η 0 lin )>0.156, z / M w is the ratio of the z-average molecular weight to the weight-average molecular weight as determined by conventional size exclusion chromatography, and log(η 0 lin ) is defined according to the double power law equation: log (the) 0 lin )=alog(m b )+blog(M w LS )+K In the formula, α=-3.8326, β=3.6954, K=-10.3477, and m b is the molecular weight per backbone bond, m b = [n c M w como +28(1-n c ) / 2, where n c is the mole fraction of α-olefin comonomer as measured by Fourier transform infrared (FTIR) spectroscopy according to ASTM D6645-01 (2001), and M w como is the molecular weight of the α-olefin comonomer in g / mole, and M w LS is the absolute weight average molecular weight determined by light scattering size exclusion.